Synergistic enhancement of syngas production from vinegar residue via air-steam co-gasification: Performance and life cycle assessment - Feng Tan; Qi Wang; Ding Jiang; Pengyu Lu; Yixuan Zheng; Shuang Wang; Mao Mu; Anqing Zheng (Biomass and Bioenergy, 2027)

An elastoplastic model for cohesionless soils under a wide range of confining pressures - Linlong Mu; Shunwei Wang; Xiaoxiang Chen; Yimin Lu (European Journal of Environmental and Civil Engineering, 2026)

A pan-cancer analysis reveals the multifaceted role of PABPC1L in immune regulation and therapy response - Kangyue Sun; Peiyi He; Lu Chen; Bonian Mu; Kai Luo; Jianqun Cai; Aimin Li; Side Liu; Yue Zhang (Functional & Integrative Genomics, 2026)

Dual-aptamer-activated RCA-MOF synergistic platform for visual detection of leukemia-derived exosomes - Ying Shen; Yunlong Xiao; Lu Liu; Suzhen Zhai; Renwu Mu; Jiahui Chen; Xiaoyan Yang; Xiaojun Wen; Chunlin Zhang; Hai Shi (Analytica Chimica Acta, 2026)

Microbial mechanisms mediate divergent ecosystem responses to nitrogen and phosphorus enrichment - Zehao Lv; Gangsheng Wang; Daifeng Xiang; Xiankai Lu; Mingkai Jiang; Donghai Wu; Qinggong Mao; Shuhao Zhou; Shanshan Qi; Zirui Mu; Yilei Zhong; Mianhai Zheng; et al. (Soil Biology and Biochemistry, 2026)

Boron-mediated pectin demethylesterification improves Na+ retention in root cell wall and alleviates salt stress in Brassica napus L. - Yu Yang; Wenjing Hao; Rui Jing; Xiaolei Feng; Diqing Yin; Muhammad Riaz; Mu Lu; Yusheng Niu; Lei Yan (Plant Science, 2026)

Geochronology and Geochemistry of Cretaceous volcanic rocks in the Central Lhasa Block, China: Constraints on the evolution of the Neo-Tethys Ocean - Zhi-Qiang Kang; Rui Wang; Chun-Xi Shan; Ji-Feng Xu; Feng Yang; Sheng-Liang Pei; Ji-Zhong Mu; Ling-Ling Wu; Lu Zhou (Journal of Asian Earth Sciences, 2026)

Efficient fractionation of reed biomass by inorganic salt-driven seawater/ethanolamine pretreatment for fermentable sugars and N-containing lignin - Hao Tong; Meizhen Jiao; Bo Mu; Bin Li; Shihao Su; Yehan Tao; Jinwen Hu; Jian Du; Jie Lu; Chenglong Fu; Haisong Wang (Chemical Engineering Journal, 2026)

Source-oriented ecological risk assessment and prioritization of heavy metals in soils impacted by coal gangue in Southwestern China - Guixiang Luo; Siyan Lv; Nan Mu; Yongmin Wang; Jiachun Lu; Cheng Zhang; Zhenwu Tang; Dingyong Wang (Applied Soil Ecology, 2026)

Origin of the heterogeneous enrichment of critical elements (Zr(Hf)-Nb(Ta)-Ga-REY) at the base of late permian tuffs, southwestern China - Tianyang Yang; Yulin Shen; Jian Shen; Lu Lu; Jun Jin; Xiwei Mu; Qinggen Bai; Aoyang Yang (International Geology Review, 2026)

Photoperiod induces alterations in redox homeostasis, immune response, and responses to light stimulation in the red swamp crayfish (Procambarus clarkii) - Lang Zhang; Qi Bai; Yingchun Mu; Yali Yu; Liting Ye; Lu Qiao; Wenya Ji; Jie Peng; Meiping Lan; Ziwei Song; Yu Fang (Aquaculture, 2026)

In vitro screening and probiotic evaluation of lactic acid bacteria exhibiting potential to enhance intestinal barrier function and antioxidant properties - Shishen Liu; Lu Feng; Haijun Mu; Shenhuizi Chen; Xue Han; Qian Xu (Food Bioscience, 2026)

A dual colorimetric and fluorescent sensor for non-enzymatic glucose detection via catalytic reaction with o-phenylenediamine mediated by carbon dot-decorated Fe3O4 nanoparticles - Wei-Bin Tseng; Wei-Kai Tsai; Ming-Mu Hsieh; Chi-Yu Lu; Po-Chiao Lin; Wei-Lung Tseng (Analytica Chimica Acta, 2026)

CD22+-apoptotic vesicles from cardiac fibroblasts provide endogenous cardioprotection against myocardial ischemia-reperfusion injury - Chan Zhang; Hao Hao; Nan Mu; Yishi Wang; Yin Yue; Lu Yu; Heng Ma (Science China Life Sciences, 2026)

Engineering-designed NIR-II carbon dots: for liver and gallbladder diagnosis and treatment - Huixian Mao; Qianwen Mu; Zhixiang Lu; Gang Liu (Science Bulletin, 2026)

Orbital symmetry matching-mediated synergistic N2/CO2 activation on Cu-Co3O4 for photocatalytic urea synthesis - Meng Qiao; Yan-Fei Mu; Ji-Li Zhou; Su-Xian Yuan; Meng-Ran Zhang; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2026)

Rate-induced Asian hydroclimate shifts at the onset of DO22 - Zhenqiu Zhang; Yongjin Wang; Ziqi Mu; Hao Lu; Dianbing Liu (Climate Dynamics, 2026)

Systematic search for optimal lanthanide titanates towards improved neutron absorption performances through reactor Monte Carlo predictions - Jiawei Mu; Yanli Shi; Guanyang Liu; Tiecheng Lu; Jianqi Qi (Annals of Nuclear Energy, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

Collaborative Optimization of Capacity and Operation Strategy for an Air-Source and Ground-Source Heat Pump Coupled Heating System - Huan Liu; Junqing Liu; Peng Li; Yanru Lu; Xiaojie Niu; Jinghui Luo; Yongchao Mu (Applied Geophysics, 2026)

Sulfur vacancy-rich MoS2 nanoflowers as electron shuttles boost Fe(VI) activation for efficient micropollutant degradation - Lian Wu; Xin Zhou; Zi-Yi Han; Hui-Zhi Mu; Lu Wang; Yu-Lei Liu; Jun Ma (Journal of Hazardous Materials, 2026)

Association of microplastic pollution with coral resilience in the presence of sea surface temperature anomalies - Xu Dong; Xiangang Hu; Kaishuo Lu; Kai Hu; Li Mu (Journal of Hazardous Materials, 2026)

Exopolysaccharides from Lactiplantibacillus plantarum Y12 enhance adhesion to HT-29 cells and gastrointestinal survival, and act synergistically with Y12 to alleviate DSS-induced colitis in mice by modulating the gut microbiota and repairing the intestinal barrier - Xiaochen Shi; Tianhao Zhang; Xueqi Lu; Meichen Sui; Zhiyan Wen; Yanfeng Tuo; Guangqing Mu; Yinglong Song (Food Bioscience, 2026)

Effect of pile corner rounding on local scour around offshore wind turbine foundations in sands using CFD–DEM - Xiangyi Meng; Yifan Lu; Xiaoming Feng; Guizhong Tian; Yadong Zhu; Zhongqiu Mu (Computers and Geotechnics, 2026)

Amorphous nickel hydroxide accelerates interfacial water dissociation for efficient electrochemical nitrate decontamination and ammonia recovery - Xiaoyu Tian; Baixian Lu; Yanyu Zhang; Chaoran Shao; Ruiyan Fan; Jiachen Xie; Qingsong Mu; Yiwei Dai; Ziyan Feng; Qi Wang; Aimin Wang (Chemical Engineering Journal, 2026)

Development and application of KASP molecular marker for accelerated breeding of low-acid Cerasus humilis cultivars - Xia-Yu Xing; Xiao-Yan Wang; Yue-Zhan Xiao; Hao-Nan Wang; Hou-Qiang Song; Ming Liu; Xiao-Peng Mu; Jian-Cheng Zhang; Lu-Ting Jia; Yu Gary Gao; Shuai Zhang; Peng-Fei Wang (Plant Cell Reports, 2026)

An ovarian follicle-based angiogenesis microphysiological system for high-efficiency screening of anti-angiogenic drugs - Xuebing Yang; Jing Liang; Nan Sun; Lu Mu; Jinfeng Xiong; Ge Wang; Kaiying Geng; Xie’an Feng; Yibo Wang; Shuo Zhang; Xueqiang Xu; Yan Zhang; et al. (Science Bulletin, 2026)

Experimental characterization and design implications on vertical dynamic response of suction bucket foundation in saturated sand - Linlong Mu; Tao Zhou; Yimin Lu (Ocean Engineering, 2026)

Alterations in the ecological amplitude of summer-dormant submerged macrophyte serve as sensitive indicators for the ecological risk of PFAS in water - Zhenhan Li; Hongwei Yu; Diga Gang; Quanlin Lu; He Ji; Jichun Mu; Xiaoyan Zheng; Jing Qi; Chengzhi Hu; Jiuhui Qu (Journal of Hazardous Materials, 2026)

Stage-specific environmental responses and divergent distributional shifts of Antarctic krill under climate change in the Cosmonaut Sea - Xiuxia Mu; Xianyong Zhao; Chongliang Zhang; Yunxia Zhao; Qingchang Xu; Jichang Zhang; Yiping Ying; Lu Liu; Jianfeng He; Peiru Luo; Xinliang Wang (Journal of Environmental Management, 2026)

LC-HRMS profiling of processing-induced formation of carcinogenic N-nitrosamines in Areca nut products - Yuan-Jhe Chang; Hsueh-Ju Lu; Yet-Ran Chen; Yi-Jhen Wang; Rajendra Bose Muthukumaran; Chiung-Wen Hu; Mu-Rong Chao (Food Chemistry, 2026)

Integration of network toxicology, transcriptomics and metabolomics reveals the novel neurotoxic mechanisms of diazepam and its metabolites - Xu Xiaodong; Li Jiaxin; Li Zimeng; Yang Zhen; Qiao Lu; Xu Jinhua; Qi Bohao; Hu Xin; Ren Yuanyuan; Li Jiongtang; Mu Yingchun (Food and Chemical Toxicology, 2026)

Fabrication of debranched pea starch beads through gellan gum self-assembly and ionic cross-linking for enhanced digestive resistance - Lu Yang; Ziyun Zhao; Hongyan Mu; Yang Qin; Liu Xiong; Shucheng Zhang; Qingjie Sun (Carbohydrate Polymers, 2026)

Experimental investigation of contaminant dispersion in vertical drainage pipes induced by toilet flushing - Di Mu; Min Chang; Lu Feng; Ruibin Li; Yan Wu; Naiping Gao (Building and Environment, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Numerical Investigation of Poisson’s Ratio Effects on Ice–Structure Interaction Using the Peridynamic Method - Yuan Zhang; Liyu Ye; Chao Wang; Xiuyuan Zhang; Dagang Zhao; Jinlei Mu; Shan Pian; Biliang Lu (Journal of Marine Science and Engineering, 2026)
The peridynamic (PD) method has been widely utilized in the numerical modelling of ice–structure interactions due to its capability to naturally capture material failure and fracture evolution. PD formulations can be categorized into bond-based and state-based models. While the bond-based model offers computational simplicity, it inherently restricts Poisson’s ratio to 1/4 in three-dimensional (3D) simulations and 1/3 in two-dimensional (2D) simulations. In contrast, the state-based model allows for arbitrary Poisson’s ratios, which is essential for accurately modelling ice mechanics, as Poisson’s ratio of ice commonly exceeds 0.33 and can reach up to 0.42. This study employs the PD method coupled with the discrete energy release rate criterion to analyze the influence of Poisson’s ratio on ice failure mechanisms and ice-induced loads in two typical scenarios: cylindrical impact on an ice disc and ice–structure interaction with a propeller blade. The benchmark compression test yielded computed Poisson’s ratios of 0.215, 0.258, 0.333, and 0.401 for prescribed values of 0.2, 0.25, 0.33, and 0.40, corresponding to relative errors of 7.5%, 3.2%, 1.02%, and 0.38%, respectively. And the fracture simulations indicate that variations in Poisson’s ratio affects ice fracture patterns and load distributions, underscoring the limitations of the bond-based PD model in accurately representing ice–structure interactions. These findings highlight the necessity of adopting state-based PD formulations for improved numerical predictions of ice-induced mechanical responses.

Functional characterization of collectin liver 1 involving antibacterial immunity and inflammation regulation in Oreochromis niloticus - Lu Deng; Xiaoxue Yin; Qingliang Zeng; Zhanyao Lin; Jiadong Li; Siqi Wu; Jianmin Ye; Liangliang Mu (Aquaculture, 2026)

Fluvial evolution model for the paleotropics in the early Triassic hyperthermal period: An example from the Shuiyuguan area in North China - Ya-Nan Shi; Longyi Shao; Christopher R. Fielding; Haojie Lian; Ya-Nan Li; Kai Zhou; Guangyuan Mu; Jing Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Efficient fabrication of PLA/PBAT/ZnO films with inverted-pyramid Micro/nanostructures for robust anti-wet pack and antimicrobial protection - Yu Du; Rong Zhou; Kai Mu; Congyuan Zhang; Changjun Guo; Jiabao Lu; Zihao Li; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2026)

Ruthenium supported on grain-boundary-induced oxygen-vacancy-rich CeO2 for efficient ammonia decomposition - Jinghua Liu; Wujian Zhang; Junhan Yang; Yongchao Zhao; Jian Guan; Zhenxiang Li; Keyi Mu; Yuchen Chen; Aimin Chen; Zongjian Liu; Chunshan Lu; Angjian Wu; et al. (Chemical Engineering Journal, 2026)

The Complete Mitochondrial Genome of a Newly Recorded Chinese Species of Diglyphus sabulosus (Hymenoptera: Eulophidae) and Insights into Its Phylogenetic Position - Lu-Chao Fang; Zhi-Qiang Ge; Ou-Yan Xi; Ze-Lu Mu; Hong-Ying Hu (Biochemical Genetics, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Combined transcriptome and metabolome analyses reveal that galactose metabolism is vital for tobacco in response to low-nitrate stress - Dong Wang; Yongchang Wen; Haoran Xie; Mingxin Mu; Xianchao Peng; Junju Li; Jixian He; Xiaoli Liu; Yifei Lu; Bi Ren; Liming Lu; Liqin Li (Journal of Genetics, 2026)

DlNAC41 and DlNAC100 transcription factors modulate longan pulp breakdown via adjusting the expression of cell wall degradation-related genes - Hui Wang; Wenlong Zhou; Xinyue Mu; Zhongqi Fan; Ruiling Zhuo; Yihui Chen; Wangjin Lu; Boqiang Li; Shiping Tian; Yifen Lin; Hetong Lin (Postharvest Biology and Technology, 2026)

Combinatorial PPTase screening and systematic metabolic engineering for high-level indigoidine production in Corynebacterium glutamicum - Jiali Zhang; Zeyu Li; Rui Lu; Junsong Xiao; Yingying Zhu; Wei Xu; Wanmeng Mu (Food Bioscience, 2026)

Numerical investigation of toilet flushing and exhaust fan operation on aerosol transmission dynamics in building drainage system - Di Mu; Min Chang; Lu Feng; Ruibin Li; Yan Wu; Naiping Gao (Building and Environment, 2026)

Environmental standard limit fluoride exposure prioritizes neurotoxicity over osteotoxicity in larval zebrafish: A benchmark dose analysis - Xiumei Yang; Xianmei Zhang; Guojun Jian; Yuanhui Zhu; Hangyu Chen; Xiaoxi Mu; Jie Li; Bijin Zhu; Hui Lu; Yan An; Tingxu Jin (Aquatic Toxicology, 2026)

Bioaccumulation and Elimination, and Risk Assessment of Diazepam in Carp (Cyprinus Carpio) - Zhen Yang; Xiaodong Xu; Ying Li; Xin Hu; Jinhua Xu; Lu Qiao; Huiwu Sun; Yingchun Mu (Bulletin of Environmental Contamination and Toxicology, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Enhanced Asian monsoon hydroclimate instability during the mid-DO21 - Ziqi Mu; Tian Ma; Hao Lu; Dianbing Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

pH-driven integrated impacts of the calcium sulfite/Fe(VI) system: In-depth insights into active species evolution and mechanisms - Kunyu Chen; Jie Wang; Xiaoxiang Cheng; Weikang Zhang; Jingwei Huang; Congwei Luo; Xinsheng Luo; Peijie Li; Yan Jin; Daoji Wu; Ruimin Mu; Jinsuo Lu (Journal of Hazardous Materials, 2026)

The synergistic effect of algal-bacterial granular sludge in a sequencing batch reactor with tetracycline-containing synthetic livestock and poultry breeding wastewater - Yuanda Du; Shoubo Zhao; Yanan Gao; Yujie Yan; Yi Kong; Wenwen Meng; Xinru Lu; Shun Zheng; Haolin Mu; Xiaojing Chen; Qiang Kong (Journal of Environmental Management, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Deoxynivalenol induces testicular inflammation via mtDNA leakage-mediated activation of the cGAS-STING pathway in mice - Haihua Huo; Gaolong Zhong; Peixuan Li; Feiyang Chen; Yunpeng Deng; Lu Guan; Jiabin Chen; Yan Wang; Xu Wang; Qingmei Chen; Jikai Wen; Yiqun Deng; et al. (Food Bioscience, 2026)

High-value utilization of hazardous solid waste for efficient electrocatalytic oxygen reduction to produce hydrogen peroxide - Bo Liu; Xiaoshuang Song; Guoxin Mu; Jiayu Feng; Fang Wang; Rui Cao; Zibin Pan; Feixiang Lu; Ping Ning; Shuo Cui; Lijuan Jia (Environmental Research, 2026)

Development and application of a distributed hydrology and soil erosion model in a semi-arid catchment, China - Ang Lu; Peng Tian; Guangju Zhao; Xingmin Mu; Xiaojing Tian; Chaojun Gu; Lin Yang; Junjian Fan (CATENA, 2026)

Minimal modification to displacement ventilation for significant improvement through air redistribution - Zi Cheng; Jingkai Wang; Zhenying Zhang; Hao Simone Wang; Yibin Lu; Zekai Mu; Jian Liu; Zhang Lin (Building and Environment, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Unravelling methylmercury formation in high-altitude Tibetan thermokarst lakes - Xia Lu; Xiaosha Liu; Zhixia Yang; Liang Li; Man Yang; Yu-Rong Liu; Baohua Gu; Cuicui Mu (Journal of Hazardous Materials, 2026)

Biomineralization and genome-based insights of Fe(III) reduction of the NaCl-tolerant Tessaracoccus oleiagri from an integral oilfield - Xinghao Liu; Jianbin Li; Fangyi Mu; Ding Dong; Dehao Lu; Jie Yang; Ting Xu; Shuyuan Deng; Fan Zhang; Yuehui She; Hao Dong (Journal of Environmental Chemical Engineering, 2026)

Recycling acid-leaching clay wastewater to synthesize bimetallic metal-organic frameworks for efficient removal of Pb2+ and UO22+ - Mingcai Ma; Bin Mu; Jiang Xu; Yushen Lu; Aiqin Wang (Journal of Environmental Sciences, 2026)

Creating syngas and sulphur from H2S and CO2 over Mo-Cu based catalyst in a dielectric barrier discharge reactor - Lu Zhao; Wenshuang Feng; Xiaoliang Mu; Kegong Fang (Fuel, 2026)

Organic carbon burial and ocean redox modulated biotic recovery after the latest Ordovician crisis - Wei Tang; Mu Liu; Heng-Ye Wei; Li-Guang Wu; Kai Lu; Jian Wang; Xian-Hua Li (Earth and Planetary Science Letters, 2026)

Effects of taurine on immunity and ammonia metabolism in large-scale loach under ammonia stress - Ruo-Yu Zhou; Lu Chen; Meng-Yang Hu; Mu-Xi Li; Yu-Xuan Fei; Mei Huang; Yun-Long Zhang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Plasma Metabolites of Kynurenine Pathway and Risk of Stroke in the General Population: A Nested Case–control Study - Yingjun Mu; Xudong Wang; Qingyao Wang; Zhenquan Lu; Zhengyuan Zhou; Shujun Gu; Hui Zuo (Translational Stroke Research, 2026)

Tracing sediment sources during rainfall events in a northern Loess Plateau catchment using geochemical and mid-infrared spectral methods - Rui Shan; Peng Tian; Ang Lu; Xiaoxue Guo; Xingmin Mu; Haoyu Zhu; Geng Ren; Guangju Zhao (Journal of Mountain Science, 2026)

Effects of Silicon Fertilizer on the Content and Composition of Volatile Organic Compounds in ‘Akiziki’ Pear - Hongmei Mu; Guodong Li; Xiao Liang; Shujun Zhang; Guodong Chu; Yingjie Wang; Jiansheng Lu; Xiao Li (Applied Fruit Science, 2026)

Genome-wide association study identifies key SNP and glutamate receptor 4 linked to heat tolerance in Zhikong scallop Chlamys farreri - Zhi Liu; Mingyi Sui; Zujing Yang; Haitao Yu; Qianqian Mu; Lijingjing Bao; Wenhui Jiang; Wei Lu; Qiang Xing; Zhenmin Bao; Xiaoting Huang (Aquaculture, 2026)

The immunosuppressive receptor FcγRIIb (CD32b) gets involved in immune response of Nile Tilapia (Oreochromis niloticus) against bacterial infection - Jiadong Li; Shumin Du; Qingliang Zeng; Zhanyao Lin; Yansong Wang; Lu Deng; Xiaoxue Yin; Yanjian Yang; Zheng Guo; LiangLiang Mu; Jianmin Ye (Aquaculture, 2026)

Quinone structure regulates sulfide-driven reactive oxygen species generation for aquatic pollutant degradation - Han-Qing Zhao; Ruihan Yu; Jiayi Liu; Hong Cheng; Aqiang Ding; Daijun Zhang; Yang Mu; Peili Lu (Water Research, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Seasonal dynamics of microbial diversity and ecological functions in the river estuary area of Loushan River - Xin Hu; Chengci Liu; Jinhua Xu; Zhiyang Zhao; Hongyu Jin; Xiaodong Xu; Lu Qiao; Zhen Yang; Jincheng Li; Mutai Bao; Lei Huang; Yingchun Mu (Journal of Hydrology, 2026)

Mechanisms of Cr (VI) reduced by nitrogen-fixing bacteria - Zi-Xiao Xue; Han-Lin Gu; Zi-Yi Mu; Yun Niu; Meng-Die Li; Zhuo Lu; Wei Zhang (Journal of Hazardous Materials, 2026)

Unveiling the black box: Multi-omics reveal how biochar supercharges synthetic biofilms for superior bioremediation - Bo Zhang; Xiaoying Hu; Lu Han; Zhen Guo; Yongqi Liu; Huiyao Li; Yuze He; Tianyu Liu; Qingyuan Pan; Yi Mu; Jianhua Qu; Hongqi Yu; et al. (Journal of Hazardous Materials, 2026)

Spatial characterization and health risk evaluation of residual phenol five years after a river pollution incident - Tingting Liu; Fengjing Song; Yiming Sun; Zhen Ding; Hao Zheng; Shixuan Hao; Hong Xu; Yan Liu; Chao Wang; Xiaomin Xie; Mu Zhu; Peixuan Shen; et al. (Journal of Hazardous Materials, 2026)

Identification and in-silico screening of ACE-inhibitory peptides from casein hydrolysate via fermentation with different probiotics - Ruiqi Ren; Lu Liu; Xiaodong Li; Xiuxiu Zhang; Min Xu; Zhixing Zhang; Xuezhen Wang; Bingbing Mu; Xianlu Zhang; Aruna Zhou (International Dairy Journal, 2026)

Hypoxanthine accumulation caused by mutations of Bombyx mori xanthine dehydrogenase triggers female sterility - Wen-qing Lai; Zhan-peng Lu; Qiang Zhang; Zuo-min Shao; Han Gao; Xia Sun; Sheng Qin; Xue-yang Wang; Mu-wang Li (Insect Biochemistry and Molecular Biology, 2026)

Combinatorial engineering of 2-C-methyl-D-erythritol 4-phosphate pathway flux optimization and key enzymes spatial organization for (−)-α-bisabolol production in Escherichia coli - Junsong Xiao; Zeyu Li; Roulin Chen; Rui Lu; Jiali Zhang; Yingying Zhu; Wanmeng Mu (Food Bioscience, 2026)

Pathway optimization and membrane engineering for highly efficient production of indigoidine in engineered Escherichia coli - Zeyu Li; Rui Lu; Heng Hu; Roulin Chen; Dingjie Zhou; Yingying Zhu; Wanmeng Mu (Bioresource Technology, 2026)

Transcriptome-wide identification of glycoRNAs by Clier-seq pipeline - Nannan Zhu; Yan-Lin Yang; Yuan-Tao Liu; Zheng-Zhou Lu; Yan Wang; Yi-Ling Luo; Ning Meng; Yan Yuan; Qian Zhong; Mu-Sheng Zeng (Science China Life Sciences, 2026)

Impact of salinity on nitrogen cycling and microbial community functional potential in groundwater of the Yellow river delta - Huan Wang; Chuanshun Zhi; Yufei Jiao; Dan Xu; Wenfeng Gao; Yawei Kou; Xiancang Wu; Jing Bai; Hui Mu; Houliang Lu; Xiaonong Hu (Applied Geochemistry, 2026)

A hybrid model driven by remotely-sensed data for simulating the impact of high spatiotemporal variations in fertilization and atmospheric N2O on N2O emissions in paddy fields - Wei Jiang; Xiang Gao; Housheng Wang; Xuerong Lang; Shuai Shen; Xian Hu; Linkai Wen; Qinchun Xu; Yan zhang; Xiaosan Jiang; Jinyang Wang; Yanfeng Ding; et al. (Agricultural and Forest Meteorology, 2026)

Signaling pathways and potential therapeutic agents in trastuzumab-induced cardiotoxicity - Haonan Zhang; Changxu Lu; Siyuan Cheng; Jingyi Wu; Anqi Hu; Zhongyi Mu; Dan Dong; Mingli Sun (Apoptosis, 2026)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Incorporating spatiotemporal structure to improve the understanding of Antarctic krill (Euphausia superba) distribution - Xiuxia Mu; Xinliang Wang; Chongliang Zhang; Xianyong Zhao; Jichang Zhang; Yunxia Zhao; Yiping Ying; Gangzhou Fan; Lu Liu; Jiancheng Zhu; Qingchang Xu (Fisheries Research, 2025)

Dynamic response of high-piled wharf under wave excitation considering local scour - Linlong Mu; Tao Zhou; Yimin Lu; Maosong Huang; Shen Zhou; Meihe Chen (Soil Dynamics and Earthquake Engineering, 2025)

Rate-dependent uplift behavior and soil failure mechanisms of suction anchors in loose sand: a transparent soil PIV study - Tao Zhou; Linlong Mu; Yimin Lu; Meihe Chen; Maosong Huang; Yuxuan Li (Ocean Engineering, 2025)

Unraveling humidity's dual effects on trace methane photocatalytic ozonation: Enhanced radical generation versus active site blockade - Junyu Ying; Yun Wang; Haiyuan Zhang; Yang Bai; Jiahua Zhu; Xiaohua Lu; Wei Li; Liwen Mu (Journal of Environmental Chemical Engineering, 2025)

Discontinuation of glacial meltwater input reshapes the diversity and stability of eukaryotic planktonic microbial communities in glacial lakes - Xiaodong Li; Qianggong Zhang; Peng Zhang; Qing Yang; Zijian Lu; Yanan Zhou; Meiqi Huang; Guangli Mu; Zhao Xue; Linyuan Lu; Yindong Tong (Environmental Research, 2025)

Induced ethanol and higher alcohols formation during CO hydrogenation over a novel MoS2-MoO3 composite catalyst - Xiaomeng Yuwen; Xiaoliang Mu; Lu Zhao; Kegong Fang (Chemical Engineering Journal, 2025)

MicroRNA-451: A multifaceted regulator in cerebral and cardiac ischemia-reperfusion injury - from molecular mechanisms to therapeutic potential - Fei-xiang Wang; Zu-an Shi; Zi-hang Yu; Bin Lu; Guo Mu (Molecular Biology Reports, 2025)

Molecular hydrogen as a novel regulator of cellular pyroptosis: mechanistic insights and therapeutic implications - Yong Ye; Zi-hang Yu; Liang Nie; Bin Lu; Guo Mu (Molecular Biology Reports, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Enhanced dispersion of mixed-dimensional palygorskite clay via high-pressure homogenization and its synergistic reinforcement in chitosan composites - Yushen Lu; Bin Mu; Yuru Kang; Wenting Gao; Aiqin Wang (Applied Clay Science, 2025)

Changes of mandibular organ, biosynthesis rate of methyl farnesoate, and their hemolymph levels during the ovarian development of the swimming crab Portunus trituberculatus - Meimei Liu; Zhijun Liu; Changkao Mu; Jianfeng Lu; Zhenpeng Kai; Xugan Wu (Aquaculture International, 2025)

Discovery of Fukuyoa yasumotoi (Dinophyceae) from the Xisha Islands, South China Sea: A comprehensive study on morphology, molecular phylogeny and toxicity - Ruifang Wang; Wenguang Zhang; Zhongyong Yan; Shiwen Zhou; Ruoyu Guo; Junjie Zheng; Xinfeng Dai; Douding Lu; Qinglin Mu; Jiangning Zeng; Mengmeng Tong; Zhun Li; et al. (Harmful Algae, 2025)

Anti-melanogenic effect and mechanism of oxypaeoniflorin derived from edible Paeonia ostii flower on melanogenesis in B16F10 cells and zebrafish - Kejie Peng; Yixuan Wang; Zhangtie Wang; Jing Wang; Yuhang Zhu; Qiannan Pan; Yumeng Li; Jian Mu; Xiuxin Zhang; Baiyi Lu (Food Bioscience, 2025)

Hierarchical solar interface evaporator derived from natural multilevel plant leaves for high-efficiency desalination - Jiujiu Tian; Xiaojiang Mu; Yitong Wang; Hailan Zhao; Lu Yin; Fan Zhang; Xiaoyang Wang; Lei Miao (Chemical Engineering Journal, 2025)

Understanding the mechanistic role of reversible LiAg alloy interphases in ultralong-cycle lithium-metal batteries - Zhongjiu Yang; Taesoon Hwang; Yuhe Mu; Jin Luo; Gustavo Felicio Perruci; Hongbing Lu; Kyeongjae Cho; Yue Zhou (Chemical Engineering Journal, 2025)

Synergistic Co single-atom/nanoparticle catalysis enables stable hydrogenation of levulinic acid to gamma-valerolactone with formic acid - He Huang; Wei Zhang; Jianrong Zeng; Mengke Liu; Han Lin; Liwen Mu; Xin Feng; Xiaohua Lu; Lilong Zhang; Jiahua Zhu (Chemical Engineering Journal, 2025)

Effects of β-hydroxy-β-methylbutyrate inclusion on growth performance and fillet quality of olive flounder Paralichthys olivaceus fed low fishmeal based diets - Chaoqing Wei; Zhenxia Su; Cancan Xia; Lu Li; Zhicheng Song; Hua Mu; Hanliang Cheng; Jianhe Xu; Zhiguo Dong; Binlun Yan; Lu Zhang (Aquaculture, 2025)

Comprehensive analysis of greenhouse gases emissions and microbial dynamics in glacier-fed lakes across various ablation stages - Shuang Liu; Fuyuan Mai; Meiqi Huang; Qing Yang; Xiaodong Li; Guangli Mu; Bingya Zhang; Linyuan Lu; Yu Pang; Ding He; Qianggong Zhang; Yiwen Liu; et al. (Water Research, 2025)

Hydrogel-engineered platforms for efficient solar interfacial evaporation: Current status and future directions - Junnan Jiang; Heyu Jin; Yao Lu; Xiaohua Liu; Hongyu Ge; Lin Mu (Journal of Water Process Engineering, 2025)

Innovative flood prediction modeling: Enhancing efficiency for large-scale simulations and analyzing responses to diverse impacting factors - Junhui Wang; Jingming Hou; Shaowu Li; Bin Lu; Yuru Yan; Yan Mu (Journal of Hydrology, 2025)

Ubiquitination: A non-negligible modulator in doxorubicin-induced cardiotoxicity - Can Gao; Changxu Lu; Jinwen Wei; Zhongyi Mu; Mingli Sun; Dan Dong; Zhenning Liu (Chemico-Biological Interactions, 2025)

Unlocking the synergistic effects in biomass-plastic Co-pyrolysis using a hybrid machine learning approach with blended rule descriptors - Peng Jiang; Wenjie She; Hao Zhang; Lin Li; Han Lin; Tuo Ji; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Biomass and Bioenergy, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

The importance of fungal necromass in soil organic carbon: Insights from elevation gradients in arid regions - Mengfei Cong; Zhihao Zhang; Guangxing Zhao; Xinping Dong; Yan Lu; Lei Li; Yang Hu; Weiqi Wang; Zhaobin Mu; Akash Tariq; Jordi Sardans; Josep Peñuelas; et al. (Applied Soil Ecology, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Polystyrene nanoplastics promote muscle cell senescence through microtubule hyper-stabilization-mediated mitophagy dysfunction and cGAS-Sting activation - Jie Cui; Xianlin Yue; Yajun Zhang; Bingjie Wang; Angela Mu; Shifeng Ren; Liwei Shao; Shanshan Zhu; Nan Zhang; Yu Lu; Hongjuan Cui; Dong Li; et al. (Journal of Hazardous Materials, 2025)

Exploring Allium mongolicum Regel flavonoids alleviation of deoxynivalenol-induced gut inflammation and flesh-quality improvement based on muscle-intestinal axis in a Channa argus model - Zhe Yu; Zhuang Xiong; Yi Wang; Zhi-Qiang Gao; Ke-Xin Lu; Ying Zhang; Mu-Yang Li; Yuan-Xi Yue (Food Bioscience, 2025)

Multi-omics investigation into microbial community succession and flavor compound dynamics during post-fermentation of Doubanjiang - Ling Chen; Wei Su; Yingchun Mu; Zhuo Chen; Yu Jiao; Linzhu L; Huayan Luo; Zhongle Lu (Food Bioscience, 2025)

Unraveling the main chemical mechanism of PM2.5 pollution caused by open burning of sugarcane straw during winter in southern China: The Pivotal Role of NOx and NH3 Oxidation-Neutralization - Xu Wei; Guiyun Liang; Jingying Mao; Junchao Yang; Yijun Mu; Chuan Nong; Dabiao Zhang; Jiahui Lu; Xishou Huang; Ying Wu; Zhaoyu Mo (Environmental Pollution, 2025)

Nature-Inspired cell membrane-coated artificial biocatalysts with Os-single-atom sites and multienzyme-Mimetic activities for targeted tumor therapy - Jiawei Wang; Jing Wu; Zijun Ma; Xin Xie; Lu Zhao; Xiao Luo; Wenjun Liu; Bo Ren; Qi Li; Ling Li; Shengdong Mu (Chemical Engineering Journal, 2025)

A rapid bag-protected micro-solid-phase extraction of polychlorinated biphenyls based on dual-ligand hollow MOF: one-stone-three-birds strategy from KMnO4 - Xuemei Wang; Jiyun Chen; Jie Zhang; Fu Mu; Zhen Zhang; Rao Peng; Xinzhen Du; Xiaoquan Lu (Chemical Engineering Journal, 2025)

Behaviors of suction bucket foundations in sands under vertical tensile load and seismic action - Xinglei Cheng; Yuming Su; Kun Mu; Dechun Lu; Jianxin Zhang; Liqiang Sun (Soil Dynamics and Earthquake Engineering, 2025)

Effects of Lactobacillus plantarum on Broiler Health: Integrated Microbial and Metabolomics Analysis - Lei Wang; Fazul Nabi; Xiaohu Zhang; Guangyu Zhou; Qurban Ali Shah; Siyuan Li; Yaozhong Lu; Siyang Mu; Xiaohui Zhu; Zhengrong Lin; Jiakui Li (Probiotics and Antimicrobial Proteins, 2025)

Investigation on the inactivation of Prorocentrum lima and degradation of diarrhetic shellfish toxins via peroxymonosulfate-based advanced oxidation process - Jiahang Mu; Zhang Kang; Jinjin Lu; Junhua Fang; Li Zhang; Kefu Zhou (Marine Pollution Bulletin, 2025)

Gradient purification of surface water and ultrafiltration membrane fouling mitigation based on Fe(VI) multifunctional integration characteristics: Is a sedimentation unit necessary? - Kunyu Chen; Jie Wang; Xiaojiang Huang; Ruimin Mu; Congwei Luo; Daoji Wu; Jing Liu; Jinsuo Lu; Xiaoxiang Cheng (Water Research, 2025)

Boron-induced phenylpropanoid metabolism, Na+/K+ homeostasis and antioxidant defense mechanisms in salt-stressed soybean seedlings - Mu Lu; Muhammad Riaz; Kaiqing Tong; Wenjing Hao; Yu Yang; Xiaomeng Zhao; Lu Wang; Yusheng Niu; Lei Yan (Journal of Hazardous Materials, 2025)

Mesoporous high-entropy-alloy electrocatalysts via electrospinning for enhanced alkaline water electrolysis - Lu Wang; Chuhao Wang; Yuhe Mu; Jingrui Fan; Xiubei Yang; Chengbing Yu; Bing Guo; Gaofeng Zeng (Fuel, 2025)

Development of a semi-automated one-step purification method for determination of 63 pesticides in fish samples by HPLC-MS/MS using natural loofah sponge as a novel adsorbent - Yupeng Wen; Wendi Huo; Xinyuan Zhang; Yingchun Mu; Huan Liu; Chaoying Zhang; Lu Qiao; Jincheng Li (Food Chemistry, 2025)

Corrigendum to “Changes of unique flavor substances and metabolic pathway brought by Lacticaseibacillus rhamnosus WH. FH-19 fermented milk during fermentation and storage stage: HS-SPME-GC-MS and HPLC-MS-based analysis” [Food Bioscience 65 (2025) 1–11/105974] - Lu Feng; Jingxia Yang; Liping Sun; Xiaoyan Zhu; Wei Lan; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2025)

Liquid metal-transition metal oxide photoactive electrode with interfacial interlocking structure for photo-enhanced asymmetric micro-supercapacitor - Yue Liang; Jian Gao; Tong Shen; Nan Lu; Tian-Sheng Mu; Yong-Chao Zhang; Xiao-Dong Zhu (Chemical Engineering Journal, 2025)

Development of cell labeling and gene editing tools in urochordate Ciona - Xiang Li; Lu Mu; Hongzhe Peng; Sun Nyunt Wai; Longjun Pu; Bo Dong (Marine Life Science & Technology, 2025)
Urochordate Ciona spp. are ideal marine model organisms for studying embryogenesis and developmental and evolutionary biology. However, the effective implementation of genetic labeling and CRISPR/Cas9-based editing tools at cellular resolution remains challenging. This study successfully developed and validated a collection of Gateway-based vectors for cell labeling in Ciona spp. The destination vector sets contained two Gateway cassettes flanked by Minos sites, allowing the N- or C-terminal tagging of a protein of interest with various fluorescent markers. In addition, we optimized the CRISPR/Cas9 and CRISPR/dCas9 systems by incorporating P2A-mCherry, a fluorescent indicator for Cas9 expression at cellular resolution. We demonstrated the effective destruction or inhibition of target genes when CRISPR constructs were introduced into fertilized eggs. Furthermore, we engineered a dual fluorescence sensor system that helps visualize successful gene knockouts at the cellular level in specific tissues. The genetic tools developed in this study offer a robust method for gene expression, cell tracking, and subcellular protein localization while also facilitating tissue-specific functional analysis in Ciona embryos and other model systems.

DEM-DDM study on the humidification uniformity of brown rice in a pan coater - Xiangyi Meng; Yadong Zhu; Zhongqiu Mu; Guizhong Tian; Xiaoming Feng; Bin Zhang; Yongsheng Pei; Yifan Lu (Biosystems Engineering, 2025)

Facile synthesis of trimetallic compounds based on cobalt and nickel with ammonium fluoride-based complex for energy storage applications - Tsai-Mu Cheng; Pei-Chen Kuo; Yi-Chun Lai; Pin-Yan Lee; Chutima Kongvarhodom; Muhammad Saukani; Sibidou Yougbaré; Hung-Ming Chen; Kuo-Chuan Ho; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Fluoride enrichment in geothermal waters based on H, O, Sr, and Li isotopes of the Taiyuan Basin, North China - Chang Lu; Ying Li; Xiaocheng Zhou; Yuwen Wang; Weiye Shao; Zhaojun Zeng; Zhaofei Liu; Dawei Liao; Hui Zhang; Huimin Mu (Journal of Asian Earth Sciences, 2025)

Isolation, identification, and virulence of three strains of Beauveria bassiana from silkworms, Bombyx mori - Qiang Zhang; Wenqing Lai; Qin Li; Xiaoying Zhang; Zhan-peng Lu; Jiawei Jiang; Wenjing Yu; Zuo-min Shao; Xue-yang Wang; Mu-wang Li (Journal of Asia-Pacific Entomology, 2025)

Microbial absolute quantification and metabolomics reveal the impact of partial KCl substitution for NaCl on the flavor quality of Zao Chili - Kangli Yang; Wei Su; Yingchun Mu; Xiaomin Liu; Yuxia Liu; Yongxin Lu (Food Bioscience, 2025)

Broflanilide induces zebrafish neurobehavioral defects by interfering with synaptic homeostasis - Kai Wang; Xiyan Mu; Xiaoyu Liu; Lu He; Chengju Wang (Aquatic Toxicology, 2025)

Study on Acoustic Emission-Resistivity Response of Hydraulic Fracturing in Rock-Like Samples - Jisheng Sui; Lianchong Li; Wenqiang Mu; Jian Lu; Liming Liu; Cheng Gu (Rock Mechanics and Rock Engineering, 2025)

Association Between Mixed Metal Exposures and Female Infertility: A Large Cross-sectional Study - Yunan He; Xiaoxiao Su; Zhiping Niu; Bolun Zhang; Hui Mu; Lu Wang; Yuanqing Yao; Xiaohong Wang (International Journal of Environmental Research, 2025)

Investigation of brittle characteristics and hydraulic fracture propagation in deep sandstone reservoirs in the central Junggar Basin - Lianchong Li; Jian Lu; Wenqiang Mu; Ran Ding; Anhai Zhong; Feng Yang; Mingyang Zhai (Bulletin of Engineering Geology and the Environment, 2025)

Corrigendum to “Recirculating aquaculture system as microbial community and water quality management strategy: a rearing mode for improved viability of crab larvae” [Water Research Volume 252, Mar 2024] - Zhibin Lu; Weichuan Lin; Qiang Li; Qingyang Wu; Zhiming Ren; Changkao Mu; Chunlin Wang; Ce Shi; Yangfang Ye (Water Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Green and recyclable photocatalytic hydrogel film with antibacterial and ethylene scavenging properties for fruit preservation. - Zewen Lu; Jingbo Mu; Chaowen Guan; Tianshuo Sui; Chuanzhi Liu; Zengcai Guo; Shimin Liao (Food Chemistry, 2025)

Solar-driven evaporation based on regulation salt crystallization behavior for high-efficiency freshwater production and salt collection - Hailan Zhao; Xiaojiang Mu; Lu Yin; Zhixiang Zhang; Yang Long; Yitong Wang; Xiaoyang Wang; Jianhua Zhou; Lei Miao (Desalination, 2025)

Comparison of elemental composition and 87Sr/86Sr-143Nd/144Nd between fossil and modern fish teeth and the significance of the enrichment of REE in deep-sea sediments - Zhijie Xu; Xiaoyu Zhang; Kongyang Zhu; Mu Huang; Miao Yu; Zheng Li; Zhongrong Qiu; Yanfang Lu (Frontiers in Marine Science, 2025)
Fossil fish teeth are important carriers of rare earth elements (REEs) in deep-sea sediments. Meanwhile, 87 Sr/ 86 Sr- 143 Nd/ 144 Nd in these fossils have been widely used in paleoceanography. However, when and how REEs enter the fish teeth remains ambiguous, which hinders elucidating the enrichment mechanism of REEs in deep-sea sediments, and the effectiveness of 87 Sr/ 86 Sr- 143 Nd/ 144 Nd in paleoceanography is doubted. This study examined the contents of REEs, major and trace elements, and 87 Sr/ 86 Sr- 143 Nd/ 144 Nd in modern fish teeth and in fossil fish teeth from deep-sea sediments. The results indicated that elemental geochemical properties and a redox environment are the main factors controlling their enrichment process in fish teeth. At least three categories of trace elements are classified during two different stages (physiological process of living fish and post-deposition of fossils): (1) elements of Type I mainly belong to IA, IIA, IIIA, IVA, and transition group with active chemical properties, entering into the fish teeth during life; (2) Type II represents elements from the IA, VA, transition elements, and Actinides groups, and are enriched uninterruptedly from the living fish teeth to the post-deposition fossils with variable valences under different redox conditions; (3) Type III are elements accumulated only after deposition under oxidizing or suboxidizing and are members of Lanthanides and rare dispersed elements groups with a large atomic radius and strong chemical activity. The distinctly different enrichment processes of Sr and Nd, 87 Sr/ 86 Sr, and 143 Nd/ 144 Nd in fossil fish teeth may represent different material sources and should be cautiously employed in paleoceanography. The continuous rehabilitation of 87 Sr/ 86 Sr in fossil fish teeth after deposition would change the original 87 Sr/ 86 Sr of seawater recorded near fish teeth but the content of Sr remains unchanged. As for 143 Nd/ 144 Nd, when Nd enters the fossils after deposition, the exchange of 143Nd/144Nd between particles and pore liquid gradually ceases due to the saturation of the isomorphism lattice. 143 Nd/ 144 Nd of fossil fish teeth may provide more information about deep seawater at the seawater-sediment interface. This study elucidates the enrichment mechanism of REEs in deep-sea sediments and the cautious utilization of 87 Sr/ 86 Sr and 143 Nd/ 144 Nd of fossils is a prerequisite.

Enhanced treatment efficiency of moxifloxacin-containing domestic wastewater in sequence batch reactors coupled with Spartina alterniflora biochar - Yuan-da Du; Yanan Gao; Mengyu Qin; Jian Liu; Shoubo Zhao; Haolin Mu; Xinru Lu; Shun Zheng; Xiaojing Chen; Zishu Wu; Qiang Kong; Jian Zhang (Journal of Water Process Engineering, 2025)

The mechanism of surface cover influences the sediment transport capacity - Kai Zhang; Ning Li; Suhua Fu; Hongli Mu; Bingjun Lu (Journal of Hydrology, 2025)

A double cross-linked film based on carboxymethyl chitosan binding with L-cysteine/ oxidized konjac glucomannan with slow-release of nisin for food preservation - Zihao Zhang; Lu Mu; Jinlong Li; Haixin Zhao; Hong-Man Hou; Gong-liang Zhang; Hongshun Hao; Jingran Bi (Food Chemistry, 2025)

Soil minerals regulate soil organic carbon accumulation through glomalin-related soil protein along an elevation gradient in a mountain arid ecosystem - Guangxing Zhao; Zhihao Zhang; Weiqi Wang; Mengfei Cong; Xinping Dong; Yanju Gao; Zhaobin Mu; Yan Lu; Lei Li; Akash Tariq; Jordi Sardans; Josep Penuelas; et al. (Environmental Research, 2025)

Crystal adjustment-based neutral-tinted nickel-tungsten-oxygen for electrochromic energy-efficient windows with wide spectral regulation - Aiyan Shi; Guojian Yang; Awais Ghani; Qinye Lu; Wenxin Ye; Chenjie Mu; Tengyao Jiang; Zhenqian Pang; Yanghua Lu; Gang Tan (Chemical Engineering Journal, 2025)

Single-chain variable fragment-based immunoassay for bioactive natural products - Xiping Cui; Jian Lu; Jinchao Wei; Suqing Zhao; Yiyong Yan; Guo Yin; Bing Wang; Yunping Mu; Peng Li (Phytochemistry Reviews, 2025)

Parkinson's Disease and the Microbiota-Gut-Brain Axis: Metabolites, Mechanisms, and Innovative Therapeutic Strategies Targeting the Gut Microbiota - Zhao Ran; Ben-Rong Mu; Dong-Mei Wang; Xin-Huang; Quan-Hong Ma; Mei-Hong Lu (Molecular Neurobiology, 2025)

3D Heterogeneous Geological Model of Natural Gas Hydrates in Shenhu Area, South China Sea - Langfeng Mu; Dawang Liu; Yi Zhang; Hailong Lu; Shipeng Wei (Journal of Marine Science and Engineering, 2025)
Natural gas hydrates, as a novel clean energy resource, have attracted widespread attention because of their highly complex reservoir properties, fluid distribution, and phase transitions. In particular, the fluid–solid interactions among hydrates, natural gas, water, and other multiphase components, along with phase state transitions influenced by temperature and pressure and the dynamic reservoir responses induced by hydrate decomposition and synthesis, make their study unique. Consequently, accurately predicting the structure and reservoir properties of natural gas hydrates remains a scientific challenge. In this study, high-resolution 3D seismic data, well logging, and core samples from the Shenhu test area in the South China Sea were utilized for stratigraphic correlation and classification. The hydrate, three-phase mixed, and free gas layers were identified as distinct geological bodies, and detailed stratigraphic subdivisions were performed based on hydrate distribution and physical properties. By integrating stochastic and deterministic modeling approaches, a comprehensive hydrate reservoir model, along with temperature and pressure field models, was established. For the first time, a three-dimensional heterogeneous geological model of the hydrate reservoir was developed for the test exploitation area. This model provides a robust geological foundation for hydrate reservoir studies, numerical simulations, and the formulation of efficient exploitation strategies, contributing to the advancement of natural gas hydrate exploration and production.

Astaxanthin ameliorates high-carbohydrate diet-induced ER stress, immunosuppression and hepatic glucose metabolism through AMPK/autophagy pathway in Channa argus - Mu-Yang Li; Yun-Zhuo Liu; Xiu-Mei Chen; Xiao-Tian Niu; Lu Chen; Lei Zhao; Gui-Qin Wang (Aquaculture, 2025)

Changes of unique flavor substances and metabolic pathway brought by Lacticaseibacillus rhamnosus WH. FH-19 fermented milk during fermentation and storage stage: HS-SPME-GC-MS and HPLC-MS-based analysis - Lu Feng; Jingxia Yang; Liping Sun; Xiaoyan Zhu; Wei Lan; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2025)

Efficient purification of exosomes and subpopulations in fresh bovine milk via fine isolation of free-flow isoelectric focusing in large scale - Muhammad Idrees Khan; Keer Chen; Lu Zhang; Shah Saud; Qiang Zhang; Hua Xiao; Zhishen Mu; Chengxi Cao (Chemical Engineering Journal, 2025)

Tailoring argyrodite electrolyte for enhanced interface compatibility with lithium anode - Shijie Lu; Yuxiang Zhang; Xinyu Zhang; Tianwen Yang; Haijian Lv; Zihan Li; Daobin Mu (Chemical Engineering Journal, 2025)

An optimized non-landslide sampling method for Landslide susceptibility evaluation using machine learning models - Shuai Xu; Yingxu Song; Pin Lu; Guizhen Mu; Ke Yang; Shangxiao Wang (Natural Hazards, 2025)

Carbon sink efficiency of Chinese mollusk mariculture - Lance Yu; Jianfeng Zhu; Xiaomu Guan; Lu Zhai; Zhuming Zhao; Yongtong Mu; Tao Liu (Aquaculture, 2025)

Integrating machine learning for multi-objective optimization of biomass conversion to hydrogen - Yinchen Li; Peng Jiang; Lin Li; Tuo Ji; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Journal of Cleaner Production, 2025)

Upcycling acid waste gas containing H2S and CO2 into syngas and sulfur by non-thermal plasma coupled with Zn-Mo/Al2O3 catalyst - Wenshuang Feng; Xiaomeng Yuwen; Xiaoliang Mu; Lu Zhao; Kegong Fang (Fuel, 2025)

A pH-responsive fluorescent film with the smartphone-assistance for real-time and visual detection of food freshness - Lu Mu; Huihui Wang; Zihao Zhang; Hong-Man Hou; Gong-Liang Zhang; Hongshun Hao; Jingran Bi (Food Chemistry, 2025)

Construction of diffusion and binding synergy in carbon-supported catalysts with varied Pd0/PdO Ratios for direct synthesis of hydrogen peroxide - Zhiheng Wang; Jiali Huang; Guancong Jiang; Tuo Ji; Han Lin; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Chemical Engineering Journal, 2025)

Thiol-linked hyaluronic acid-mediated encapsulation of RCR-stabilized gold nanoclusters for hyaluronidase sensing and cellular imaging - Manivannan Madhu; Meng-Yuan Tsai; Ming-Mu Hsieh; En-Yu Lin; Wei-Bin Tseng; Chi-Yu Lu; Wei-Lung Tseng (Carbohydrate Polymers, 2025)

AMPK activation by dietary acadesine improves fillet texture in large yellow croaker (Larimichthys crocea) fed a linseed oil-based diet - Shengdi Chen; Zihan Sun; Ningning Liu; Chenbin Yang; Na Li; Lu Li; Chaoqing Wei; Binlun Yan; Huan Gao; Peng Tan; Hua Mu (Aquaculture, 2025)

Engineering molecular bridges for fabricating cross-linked LM-HPDMS highly sensitive capacitive sensors for wearable monitoring - Xiaoyao Zhou; Yongguang Yu; Lisong Dong; Qilong Zhou; Danyang Cao; Jiahua Zhu; Xiaohua Lu; Liwen Mu (Chemical Engineering Journal, 2025)

Mutation of MeMinD increased amyloplast size with a changed starch granule morphologenesis and structures in cassava storage roots - Xiaohua Lu; Yajie Wang; Mu Pan; Songbi Chen; Ruimei Li; Mengting Geng; Yinhua Chen; Jiao Liu; Jianchun Guo; Yuan Yao (Carbohydrate Polymers, 2025)

Interaction between resveratrol and SIRT1: role in neurodegenerative diseases - Lin Zhu; Miaomiao Yang; Lehao Fan; Qiuying Yan; Lifeng Zhang; Ping Mu; Fangjin Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Characterization of deoxynivalenol dehydrogenase from Pelagibacterium sp. SCN 63–126 and its application - Wei Xu; Jiayi Yao; Jingbo Ma; Chen Lu; Chenfei Wang; Yurong Sun; Cuie Guang; Wanmeng Mu (Archives of Microbiology, 2025)

The Characteristics of Sex Differentiation Based on Morphological Traits During the Early Development Stage of the Swimming Crab Portunus trituberculatus and Sex Prediction Model Comparison - Yanqing Peng; Junkai Lu; Ronghua Li; Chendong Xu; Shangbiao Zheng; Zhiming Ren; Chuan He; Changkao Mu; Weiwei Song; Chunlin Wang (Fishes, 2024)
To investigate the morphological traits of different sexes during the early development stage of the swimming crab Portunus trituberculatus, the genetic sex of 405 crablets from stages C I–V was determined using sex-linked molecular markers. The external appearance of each crab was observed, and the morphological traits, including carapace length (CL), full carapace width (FCW), abdomen width (AW), and abdomen length (AL), were measured to compare the differences between the sexes and to develop non-intrusive methods for sex identification. The genetic sex identification demonstrated that the female-to-male sex ratio at each stage did not deviate from 1:1. The gonopores of the females were first observed at stage C I using a scanning electron microscope; however, the shape difference in the abdominal flap between the sexes from stages C I to stage C V were not observed under a dissecting microscope. Correlation analysis showed that AW3 and AW4 were significantly correlated with sex at stage C V. Three methods were used to predict the sex of the crablets according to the morphological measurements; among them, the multinomial logistic regression (MLR) model performed better than the threshold method or the stepwise discriminant analysis, and the accuracy at stage C V increased to 90% when detailed abdominal parameters were included. These results indicate that it is feasible to predict sex during the early development stages of P. trituberculatus through morphometric and geometric parameters, which would be helpful for the creation of monosex populations of this species.

Endoplasmic reticulum stress and Ca2+ dysregulation in response to ammonia nitrogen exposure could be alleviated by dietary fermented mulberry leaf meal in Megalobrama amblycephala - Wenqiang Jiang; Linjie Qian; Qiaoqiao Mu; Yan Lin; Siyue Lu; Zhengyan Gu; Huaishun Shen; Xianping Ge; Linghong Miao (Aquaculture, 2024)

Genetic evidence linking retinol to birth weight: A two-sample Mendelian randomization study - Fangxiang Mu; Kexin Wang; Lu Jiang; Fang Wang (Reproductive Toxicology, 2024)

Highly dispersed CuOx decorated ZnO photocatalyst for low-concentration methane removal - Yun Wang; Sheng Xu; Haiyuan Zhang; Yuyin Wang; Enmao Wang; Zeyu He; Jiahua Zhu; Xiaohua Lu; Lilong Zhang; Yang Bai; Kunfeng Zhao; Qingwei Gao; et al. (Journal of Environmental Chemical Engineering, 2024)

Net primary productivity of paleo-peatlands linked to deep-time glacial periods in the late Carboniferous and early Permian icehouse interval - Yanwen Shao; Fenghua Zhao; Baruch Spiro; Dehui Li; Guangyuan Mu; Jiangman Chu; Jing Lu; Longyi Shao (International Journal of Coal Geology, 2024)

Effect of the quorum sensing signal molecule auto-inducer-2 on fermentation performance of Lactobacillus delbrueckii subsp. Bulgaricus DPUL-F36 - Xueqi Lu; Mengying Sun; Yuqing Chen; Dashuai He; Yanfeng Tuo; Guangqing Mu; Yinglong Song (Food Bioscience, 2024)

In vitro fermentation of V-type starch inclusion complexes: The controlled release of ferulic acid and beneficial modulation of the gut microbiota - Shiyi Lu; Gengjie Cui; Yifan Mu; Kaige Li; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Bioscience, 2024)

Modelling the frost cracking behavior in clayey soils: A peridynamic approach - Junwei Zheng; Jian Wang; Yang Lu; Xin Gu; Manuel Pastor; Saeid Moussavi Tayyebi; Yanhu Mu; Tian Wang (Computers and Geotechnics, 2024)

Risk assessment of cough droplets in both static and dynamic indoor environments with different ventilation strategies - Kaijun Li; Ruibin Li; Lingjun Xiao; Lu Feng; Di Mu; Xing Shi; Naiping Gao (Building and Environment, 2024)

Durability and Permeability Characteristics of Consolidated Bodies After Grouting in Freeze–Thaw Rock in Cold Regions - Xin Wang; Wenqiang Mu; Lianchong Li; Tianhong Yang; Jiang An; Jian Lu (Rock Mechanics and Rock Engineering, 2024)

Overlooked drivers of the greenhouse effect: The nutrient-methane nexus mediated by submerged macrophytes - Jichun Mu; Zhenhan Li; Quanlin Lu; Hongwei Yu; Chengzhi Hu; Yujing Mu; Jiuhui Qu (Water Research, 2024)

Depth-dependent responses of soil bacterial communities to salinity in an arid region - Xinping Dong; Zhihao Zhang; Yan Lu; Li Li; Yi Du; Akash Tariq; Yanju Gao; Zhaobin Mu; Yuhe Zhu; Weiqi Wang; Jordi Sardans; Josep Peñuelas; et al. (Science of The Total Environment, 2024)

Efficient enrichment and sensitive detection of polychlorinated biphenyls using nanoflower MIL-on-UiO as solid-phase microextraction fiber coating - Mengyao Mu; Shiping Zhu; Yanmei Gao; Ning Zhang; Youmei Wang; Minghua Lu (Food Chemistry, 2024)

Transgenerational and parental impacts of acrylamide exposure on Caenorhabditis elegans: Physiological, behavioral, and genetic mechanisms - Yajuan Chen; Zihan Liu; Weijia Yuan; Shan Lu; Weidong Bai; Qinlu Lin; Jianfei Mu; Jianqiang Wang; Haifang Wang; Ying Liang (Environmental Pollution, 2024)

Preparation, structural properties, and in vitro and in vivo activities of peptides against dipeptidyl peptidase IV (DPP-IV) and α-glucosidase: a general review - Xinxin Mu; Rongchun Wang; Cuilin Cheng; Ying Ma; Yingchun Zhang; Weihong Lu (Critical Reviews in Food Science and Nutrition, 2024)

Facing the solid waste of cotton straw and plastic mulch film mixture in China: Centralized or decentralized pyrolysis facility? - Hao Zhang; Peng Jiang; Guanhan Zhao; Lin Li; Minjiao Chen; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Waste Management, 2024)

Sources and formation characteristics of particulate nitrate in the Pearl River Delta region of China: Insights from three-year online observations - Jisheng Zhang; Zheng Zong; Chenglei Pei; Qinyi Li; Liubin Huang; Jiangshan Mu; Yue Sun; Yuhong Liu; Haibiao Chen; Dawei Lu; Likun Xue; Wenxing Wang (Science of The Total Environment, 2024)

A new type of dolomicrite envelope formed in Oligocene lacustrine sediments and its significance for preserving porosity, Bohai Bay Basin, North China - Caineng Mu; Xiaobo Huang; Liya Da; Anqing Chen; James G. Ogg; Huan Lu; Yuzhu Ge; Jian Luo; Siyu Xiong; Haiyang Cao; Mingcai Hou (Sedimentary Geology, 2024)

Coal-based graphene formation by CO2 laser scribing: Various structures and excellent electrochemical performance - Yungang Zhao; Shaoqing Wang; Xiaoling Wang; Lu Zhang; Jidun Sha; Xiaomei Zhang; Ruifeng Mu; Zeyu Dong (Fuel, 2024)

Advancing electrodialysis: Harnessing the potential of spiral-wound membrane stacks for improved desalination-efficiency and cost-efficiency - Junjie Mu; Yuyang Yao; Jikuan Wang; Yueyue Lu; Junbin Liao; Arcadio Sotto; Jiangnan Shen (Desalination, 2024)

The mechanism of MMP14-positive tumor-associated fibroblast subsets in inhibiting PD-1 immunotherapy for esophageal cancer through exosomal tsRNA-10522 - Juzheng Wang; Chunlong Zheng; Jiayu Lu; Xinyao Xu; Guangyu Xiang; Jiahe Li; Jipeng Zhang; Xiaorong Mu; Qiang Lu (Functional & Integrative Genomics, 2024)

Effect of Foliar Application of Selenite On Organic Se and Antioxidant Activity in Kiwifruit - Yun-mei Lu; Mao Mu; Li-ai Wang; Ren-hua Huang (Applied Fruit Science, 2024)

Modeling Rip Current Systems around Multiple Submerged Breakwaters - Jie Xu; Yuchuan Wang; Baoying Mu; Huan Du; Yanlei Li; Zaijin You; Sheng Yan; Lixin Lu (Journal of Marine Science and Engineering, 2024)
Multiple submerged breakwaters (MSBWs) are commonly used coastal protection structures due to their specific advantages over the emerged ones. Rip currents, as the inevitable natural hazard in the gaps of these constructions, are investigated numerically in the present study. A fully nonlinear mild-slope equation (NMSE) model possessing both fully nonlinear and fully dispersive properties is validated and adopted in the simulations. With four monochromatic wave conditions of different wave heights, periods and incidences representing low-energy, typical, storm and oblique waves tested, the flow patterns and the low-frequency oscillations of the rip currents are studied. For the convenience of risk assessment, the rip risk level is divided into three degrees according to the maximum rip flow speed. The effects of the configurations of the MSBWs on the rip current system as well as the rip risk level are examined, considering different breakwater widths, heights, forms, gap widths and gap numbers. Simulation results suggest that the cross-shore configurations of MSBWs influence the rip risk level by inducing different wave energy dissipations but the longshore configurations of MSBWs by changing flow field patterns.

Exploring the viability of peracetic acid-mediated antibiotic degradation in wastewater through activation with electrogenerated HClO - Wang Lu; Nan Chen; Chuanping Feng; Ignasi Sirés; Ning An; Haotian Mu (Water Research, 2024)

Evaluation of the collapse susceptibility of loess using machine learning - Qing-yi Mu; Tian-qi Song; Zhao Lu; Te Xiao; Li-min Zhang (Transportation Geotechnics, 2024)

Effects of neonicotinoid residues on non-target soil animals: A case study of meta-analysis - Yuxuan Cao; Wenting Zhao; Jinrui Zhang; Daniel M. Figueiredo; Mingyu Zhao; Siyang Ren; Hongyu Mu; Yiyi Li; Huan Lu; Haoyuan Shi; Xin Li; Jindong Li; et al. (Journal of Hazardous Materials, 2024)

Turning trash into treasure: Integrating waste MXene sediment with bagasse into photothermal composite aerogel for efficient solar-driven interfacial evaporation - Xiaoyan Lu; Chunxia Mu; Liqin Nong; Changlan Lan; Zhangfa Tong; Kelei Huang (Chemical Engineering Journal, 2024)

Versatile additive for enhancing the stability of Zn Anode: Pyrrolidine-based ionic liquid - Kailimai Su; Hong Zhang; Yan Wang; Xingyun Zhang; Yongbiao Mu; Zhibin Lu; Ye Han; Shanhong Wan; Junwei Lang (Chemical Engineering Journal, 2024)

Ultrasonic disaggregation of mixed-dimensional palygorskite clay for improving ABS resin properties - Jiang Xu; Lei Wu; Bin Mu; Yushen Lu; Qin Wang; Aiqin Wang (Applied Clay Science, 2024)

Ecological succession of eukaryotic community in epiphytic biofilms on Hydrilla verticillata in wetlands under norfloxacin stress - Xiaoying Mu; Songhe Zhang; Jianhui Lu; Ziqiu Zhang; Yingying Song (Process Safety and Environmental Protection, 2024)

Circ-IP6K2 suppresses tumor progression by modulating the miR-1292-5p/CAMK2N1 signal in clear cell renal cell carcinoma - Jian-ying Tang; Lu Yang; Qing-Jian Wu; Ying Yang; Yuan-Yuan Su; Yi-Rong Chen; Jiao Mu (Functional & Integrative Genomics, 2024)

Morphological, phylogenetic and metabolite profile of Prorocentrum clipeus, a newly recorded epiphytic dinoflagellate in the northern Yellow Sea - Ruifang Wang; Mengmeng Tong; Shiwen Zhou; Junjie Zheng; Wenguang Zhang; Xinfeng Dai; Douding Lu; Jiarong Hu; Tianze Leng; Qinglin Mu; Zhongyong Yan; Jiangning Zeng; et al. (Acta Oceanologica Sinica, 2024)

The construction of Cs3MoxSbyBr9/BiVO4 S-scheme heterojunction photocatalyst for efficient photocatalytic N2 fixation - Zhao-Lei Liu; Han-Ying Luo; Meng-Ran Zhang; Yan-Fei Mu; Fu-Quan Bai; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2024)

Characterization of cotinine degradation in a newly isolated Gram-negative strain Pseudomonas sp. JH-2 - Kexin Wang; Lu Xu; Jiale Ma; Ying Zhou; Yinhu Jiang; Jie Zha; Yanqiu Cai; Jian He; Jiandong Jiang; Jiguo Qiu; Yang Mu (Archives of Microbiology, 2024)

Two new anti-inflammatory compounds from the roots and rhizomes of Clematis terniflora var . manshurica (Rupr.) Ohwi - Ping Shao; Sheng Dong; Lin-Tong Mu; Ling Han; Chong-Ning Lv; Jiu-Zhi Yuan; Jin-Cai Lu (Natural Product Research, 2024)

Fermented bile acids improved growth performance and intestinal health by altering metabolic profiles and intestinal microbiome in Micropterus salmoides - Qing Guo; Wenwen Liu; Lu Zhao; Yiming Sui; Houfa Zhao; Yining Liu; Cuimin Mu; Xuepeng Wang (Fish & Shellfish Immunology, 2024)

Monitoring of chlorophyll content in local saltwort species Suaeda salsa under water and salt stress based on the PROSAIL-D model in coastal wetland - Sen Zhang; Jia Tian; Xia Lu; Qingjiu Tian; Shuang He; Yali Lin; Shan Li; Wei Zheng; Tao Wen; Xinyuan Mu; Jun Zhang; Yurong Li (Remote Sensing of Environment, 2024)

Fate and removal of fluoroquinolone antibiotics in mesocosmic wetlands: Impact on wetland performance, resistance genes and microbial communities - Xiaoying Mu; Songhe Zhang; Jianhui Lu; Yangrui Huang; Jianghao Ji (Journal of Hazardous Materials, 2024)

In-situ curing poly(N,N'-Methylenebisacrylamide)-based composite electrolyte reinforced with high-strength glass fiber skeleton for solid state lithium ion batteries - Yuxiang Zhang; Shijie Lu; Zhikun Zhao; Xinyu Zhang; Haijian Lv; Zhuolin Yang; Wenbin Sun; Man Xie; Daobin Mu (Chemical Engineering Journal, 2024)

Screening and identification of probiotics from the intestinal tract of largemouth bass (Micropterus salmoides) for use as a feed additive and bacterial infection control - Lu Xia; Gaofeng Cheng; Pan Wang; Xinyou Wang; Zhaoran Dong; Qingjiang Mu; Jiaqian Yu; Zhihao Jiang; Jun Xiao; Hao Feng; Xiangping Li; Weiguang Kong; et al. (Aquaculture, 2024)

Recirculating aquaculture system as microbial community and water quality management strategy in the larviculture of Scylla paramamosain - Zhibin Lu; Weichuan Lin; Qiang Li; Qingyang Wu; Zhiming Ren; Changkao Mu; Chunlin Wang; Ce Shi; Yangfang Ye (Water Research, 2024)

Well-defined Fe3O4@MIL-100(Fe) hollow nanoflower heterostructures for selective dection and monitoring of benzoylurea insecticides from food and water - Ning Zhang; Mengyao Mu; Shiping Zhu; Yanmei Gao; Minghua Lu (Food Chemistry, 2024)

Genetically engineering of Saccharomyces cerevisiae for enhanced oral delivery vaccine vehicle - Baoquan Han; Feng Yue; Xiaojun Zhang; Kun Xu; Zhiying Zhang; Zhongyi Sun; Lu Mu; Xiaoyu Li (Fish & Shellfish Immunology, 2024)

Microscopic insights into suction bucket installation in sand: Coupled coarse-grained CFD-DEM simulations - Peiyun Zhang; Linlong Mu; Yimin Lu; Maosong Huang; Jianguo Sun (Computers and Geotechnics, 2024)

Embedding hydrogel electrodes into hydrogel Electrolyte: An 3D protecting strategy for stretchable High-Performance supercapacitor - Chuanling Mu; Jun Fang; Junlian Nie; Lu Fu; Wen Li (Chemical Engineering Journal, 2024)

Hexabromocyclododecane-induced reproductive toxicity in Brachionus plicatilis: Impacts and assessment - Na Lu; Yaya Zhang; Qinglin Mu; Yijun Li; Yuanyuan Li; Zhongyong Yan; You Wang (Aquatic Toxicology, 2024)

Epidural administration of large dose of opioid μ receptor agonist may impair cardiac functions and myocardial viability via desensitizing transient receptor potential vanilloid 1 - Xiang Ma; Zheng Guo; Mu-Rong Li; Lu Chen; Xing Zhao; Tian-Qi Wang; Tao Sun (Toxicology and Applied Pharmacology, 2024)

The potential and prospects of modified biochar for comprehensive management of salt-affected soils and plants: A critical review - Guang Gao; Lei Yan; Kaiqing Tong; Hualong Yu; Mu Lu; Lu Wang; Yusheng Niu (Science of The Total Environment, 2024)

Integrated control strategy for dual sludge ages in the high-concentration powder carrier bio-fluidized bed (HPB) technology: Enhancing municipal wastewater treatment efficiency - Chengxian Wang; Xiaoli Chai; Bin Lu; Wei Lu; Hongbo Han; Yue Mu; Qun Gu; Boran Wu (Journal of Environmental Management, 2024)

Unsymmetric design of self-supported sheet electrode: Breaking the tradeoff between electrical conduction and surface wetting for fast energy storage and excellent cycling stability - Bin Zhang; Ze Zhang; Yuefeng Qiu; Zhiheng Wang; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Fuel, 2024)

Screening of anti-allergic Lactiplantibacillus species by splenocyte sensitization model and evaluate their probiotic and postbiotic characteristics - Lu Feng; Zihao Guo; Jinghong Zhao; Wenpu Yao; Xinling Li; Linying Wu; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2024)

Composite aerogel incorporating low temperature phase change microcapsules for enhanced thermal insulation - Bin Yan; Min Li; Honglang Lu; Menghan Pi; Jiahao Mu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Numerical simulation of fracture propagation in child wells considering dual-stress field - Shuxing Mu; Yuxuan Liu; Qianli Lu; Jianchun Guo; Hao Yu (European Journal of Environmental and Civil Engineering, 2024)

Comparative evaluation of soybean meal vs. extruded soybean meal as a replacer for fishmeal in diets of olive flounder (Paralichthys olivaceus): Effects on growth performance and muscle quality - Nannan Shen; Zhicheng Song; Cancan Xia; Hua Mu; Xiangning Chen; Hanliang Cheng; Jianhe Xu; Yongkai Sun; Chaoqing Wei; Lu Zhang (Aquaculture, 2024)

Nano-biosensor based on manganese dioxide nanosheets and carbon dots for dual-mode determination of Staphylococcus aureus - Xue Gao; Hongmei Zhang; Lu Liu; Mu Jia; Xuepeng Li; Jianrong Li (Food Chemistry, 2024)

Numerical simulation and coupling mechanism study of acoustic-inertial micromixer - Shuoshuo Mu; Yuwen Lu; Guorui Zhu (Chemical Engineering Journal, 2024)

Coupling of submerged macrophytes and epiphytic biofilms reduced methane emissions from wetlands: Evidenced by an antibiotic inhibition experiment - Jianhui Lu; Xiaoying Mu; Songhe Zhang; Yingying Song; Yu Ma; Min Luo; Rufei Duan (Science of The Total Environment, 2023)

Elucidation of the neutralizing antibody evasion of emergent SARS-CoV-2 Omicron sub-lineages using structural analysis - Cong Sun; Yuan-Tao Liu; Yin-Feng Kang; Chu Xie; Shu-Xin Li; Yu-Tong Lu; Mu-Sheng Zeng (Science China Life Sciences, 2023)

Analyzing the cellular and molecular atlas of ovarian mesenchymal cells provides a strategy against female reproductive aging - Longzhong Jia; Wenji Wang; Jing Liang; Shudong Niu; Yibo Wang; Jian Yang; Lingyu Li; Ge Wang; Xueqiang Xu; Lu Mu; Kaixin Cheng; Xuebing Yang; et al. (Science China Life Sciences, 2023)

Targeting mitophagy for neurological disorders treatment: advances in drugs and non-drug approaches - Xiong Yang; Yu Zhang; Jia-xin Luo; Tao Zhu; Zhao Ran; Ben-Rong Mu; Mei-Hong Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

The neurobehavioral impacts of typical antibiotics toward zebrafish larvae - Yining Zhang; Xue Li; Zaiteng Liu; Xiaoyu Zhao; Lu Chen; Guijie Hao; Xueping Ye; Shunlong Meng; Guohua Xiao; Jiandong Mu; Xiyan Mu; Jing Qiu; et al. (Chemosphere, 2023)

Bisphenol analogues induced social defects and neural impairment in zebrafish - Xiyan Mu; Zaiteng Liu; Xiaoyu Zhao; Lu Chen; Qi Jia; Chengju Wang; Tiejun Li; Yuanming Guo; Jing Qiu; Yongzhong Qian (Science of The Total Environment, 2023)

Thiocarbonyl fluoride generated in situ from difluorocarbene for cyclization of vicinal X-H substituted amines (X = N, O or S) - Jia-Lu Hu; Mu-Xian Fu; Ji-Chang Xiao; Jin-Hong Lin (Journal of Fluorine Chemistry, 2023)

Life cycle assessment of carbon-based adsorbent preparation from algal biomass - Shuang Wang; Wanming Lu; Sivakumar Esakkimuthu; Hao Chen; Jingwen Yang; Mao Mu; Xun Gong (Journal of Cleaner Production, 2023)

Graphene-based biomimetic array film for simultaneous fog water harvesting and wind power generation - Tsung Han Huang; Mu-Jie Shih; Yi-Yun Chen; Hannah Faye M. Austria; Owen Setiawan; Chunrui Wu; Xiaolong Lu; Lin Zhang; Wei-Song Hung (Chemical Engineering Journal, 2023)

Design of magnetic multivariate metal–organic framework for high-efficient adsorption and rapid magnetic separation of bisphenol pollutants - Yanmei Gao; Shiping Zhu; Mengyao Mu; Dongxue Li; Minghua Lu (Chemical Engineering Journal, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Bioaccumulation and elimination, acute toxicity analysis and risk assessment of diflubenzuron in common carp (Cyprinus carpio) - Lu Qiao; Lu Chen; Zhen Yang; Jinhua Xu; Jinlong Song; Xingyang Li; Huiwu Sun; Yingchun Mu (Chemosphere, 2023)

Molecular mechanism by which StSN2 overexpression inhibits the enzymatic browning of potato - Li-qin Li; Yu-lu Mu; Jing Chen; Qiang Wang; Yi-fei Lu; Sun Xin; Shi-min Yang; Xue-li Huang; Xi-yao Wang; Li-ming Lu (Postharvest Biology and Technology, 2023)

Assessing the timing and the duration of exposure to air pollution on cardiometabolic biomarkers in patients suspected of coronary artery disease - Kexin Zhu; Zhihui Hou; Conghong Huang; Muwu Xu; Lina Mu; Guan Yu; Joel D. Kaufman; Meng Wang; Bin Lu (Environmental Research, 2023)

Hydro-mechanical behavior of unsaturated intact paleosol and intact loess - Qingyi Mu; Longlong Meng; Zhao Lu; Limin Zhang (Engineering Geology, 2023)

Synergistic generation mechanisms of SOA and ozone from the photochemical oxidation of 1,3,5-trimethylbenzene: Influence of precursors ratio, temperature and radiation intensity - Hao Zhang; Hong Li; Yujie Zhang; Xuezhong Wang; Fang Bi; Lingshuo Meng; Yunfeng Li; Lu Zhao; Xin Zhang; Zhijian Peng; Yujing Mu; Wahid Mellouki; et al. (Atmospheric Research, 2023)

Silibinin exerts neuroprotective effects against cerebral hypoxia/reoxygenation injury by activating the GAS6/Axl pathway - Weiping Li; Zhe Zhang; Jiawen Li; Jun Mu; Meng Sun; Xue Wu; Xiaochen Niu; Yang Yang; Huanle Yan; Xiaoling Xu; Chengxu Xue; Lu Qian; et al. (Toxicology, 2023)

Seismic behaviour of plate-reinforced composite coupling beams with RC slabs - Jianbo Tian; Yong Zhao; Penggang Tian; Wengeng Ren; Zhe Li; Lin Mu; Junlong Lu (Soil Dynamics and Earthquake Engineering, 2023)

Intercellular mitochondrial component transfer triggers ischemic cardiac fibrosis - Chan Zhang; Hao Hao; Yishi Wang; Nan Mu; Wenhua Jiang; Zihui Zhang; Yue Yin; Lu Yu; Alex Chia Yu Chang; Heng Ma (Science Bulletin, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

The time-varying relationship between CO2 emissions, heterogeneous energy consumption, and economic growth in China - Liang Xie; Xianzhong Mu; Kuanyuting Lu; Dongou Hu; Guangwen Hu (Environment, Development and Sustainability, 2023)

Indoxyl sulfate in atherosclerosis - Cong Lu; Li Wu; Mu-Yao Tang; Yi-Fan Liu; Lei Liu; Xi-Ya Liu; Chun Zhang; Liang Huang (Toxicology Letters, 2023)

Visualizing sub-layer structural transformation in carbonized wood tracheid by Raman mapping - Jingjing Xiong; Binbin Xu; Bin Zhang; Peng Jiang; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Fuel, 2023)

Optimizing microstructure of polyelectrolyte ion exchange membrane for electrodialysis - Jin Cheng; Weiyu Zhou; Meifeng Zhu; Zekai Zhang; Yijie Lu; Yakun Chen; Hongchun Mu; Cheng Lian; Honglai Liu (Chemical Engineering Journal, 2023)

State constrained control strategy for unmanned surface vehicle trajectory tracking based on improved barrier Lyapunov function - Dongdong Mu; Lu Li; Guofeng Wang; Yunsheng Fan; Yongsheng Zhao; Xiaojie Sun (Ocean Engineering, 2023)

Underlying mechanisms for natural organic matters mediated aerobic ciprofloxacin transformation by sulfide - Han-Qing Zhao; Peili Lu; Fei Chen; Hongcheng Bai; Chen-Xuan Li; Guan-Nan Zhou; Jing Wang; Lilan Zhang; Yang Mu (Journal of Environmental Chemical Engineering, 2023)

Volcanism and wildfire associated with deep-time deglaciation during the Artinskian (early Permian) - Ye Wang; Jing Lu; Minfang Yang; Joyce A. Yager; Sarah E. Greene; Ruoyu Sun; Xiaomiao Mu; Xiao Bian; Peixin Zhang; Longyi Shao; Jason Hilton (Global and Planetary Change, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Dynamic Distribution of Mesanophrys sp. and Tissue Enzyme Activities in Experimentally Infected Mud Crab Scylla paramamosain - Kexin Zhang; Weiren Zhang; Ronghua Li; Junkai Lu; Qingwei Chen; Haojie Hu; Fei Yin; Changkao Mu; Weiwei Song; Chunlin Wang (Fishes, 2023)
Mesanophrys sp. is reported to be highly pathogenic to marine crustaceans. This study presents the first report of Mesanophrys sp. infection in the mud crab (Scylla paramamosain). In this study, we first recorded the survival rates of an experimentally infected group and a control group; the cumulative survival rate in the infected group was significantly lower compared to the control group after 72 h (73.20% vs. 94.19%), while the highest mortality of S. paramamosain occurred within the first 24 h post-infection. Then, we investigated the dynamic distribution and tissue tropism of the Mesanophrys sp. in the infected S. paramamosain by a quantitative real-time polymerase chain reaction (qPCR). The result showed that a significant increase in the number of Mesanophrys sp. could be detected in all tested tissues (obtained from the eyestalks, gills, heart, nerves, muscles and hepatopancreas) at 3 h post-infection. The numbers of Mesanophrys sp. in the gill, eyestalk and nerve tissues were relatively higher than in the other tissues. The gill tissue showed the highest numbers from 6 to 48 h. Histopathological observation found a severe collapse in the filament structure, which indicated tissue-specific pathogen infection. Furthermore, the antioxidant enzyme activity of superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) in three representative tissues (gill, muscle and hepatopancreas) were compared between the infected and control groups, and a significant increase in enzyme activity was observed in all three tested tissues in the infected group, indicating a relatively strong innate immune defense reaction that could have been induced by Mesanophrys sp. infection. These results will be helpful to Mesanophrys sp. pathogenicity-related research and the control of this pathogen in S. Paramamosain in the future.

Bamboo-based magnetic activated carbon for efficient removal of sulfadiazine: Application and adsorption mechanism - Fan Yang; Can Jin; Sen Wang; Yujie Wang; Lu Wei; Longhui Zheng; Haiping Gu; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Chemosphere, 2023)

Derivation of copper water quality criteria in Bohai Bay for the protection of local aquatic life and the ecological risk assessment - Yang Li; Di Mu; Hong-Qing Wu; Hai-Jiao Liu; Yong-Hui Wang; Guo-Chen Ma; Xue-Min Duan; Jian-Jun Zhou; Chun-Ming Zhang; Xing-Hua Lu; Xian-Hua Liu; Jun Sun; et al. (Marine Pollution Bulletin, 2023)

Sequence-paleogeography and coal accumulation of the Late Carboniferous – Early Permian paralic successions in western Shandong Province, northern China - Yanwen Shao; Fenghua Zhao; Guangyuan Mu; Bin Sun; Kaihua Liang; Dongdong Wang; Jing Lu; Shimin Ma; Longyi Shao (Marine and Petroleum Geology, 2023)

Synthesis of spindle-like amino-modified Zn/Fe bimetallic metal-organic frameworks as sorbents for dispersive solid-phase extraction and preconcentration of phytohormoes in vegetable samples - Peige Qin; Dengke Chen; Dan Li; Mengyuan Li; Mengyao Mu; Yanmei Gao; Shiping Zhu; Minghua Lu (Food Chemistry, 2023)

A sensitive ratiometric fluorescent chemosensor for visual and wearable mercury (II) recognition in river prawn and water samples - Meirong Qi; Zihao Zhang; Lu Li; Xiaoyue Mu; Yue Wang (Food Chemistry, 2023)

Effects of cascading reservoirs on streamflow and sediment load with machine learning reconstructed time series in the upper Yellow River basin - Junjian Fan; Guangju Zhao; Xingmin Mu; Ang Lu; Peng Tian; Peng Gao; Wenyi Sun (CATENA, 2023)

High carbon emissions from thermokarst lakes and their determinants in the Tibet Plateau - Cuicui Mu; Mei Mu; Xiaodong Wu; Lin Jia; Chenyan Fan; Xiaoqing Peng; Chien‐Lu Ping; Qingbai Wu; Cunde Xiao; Jianbao Liu (Global Change Biology, 2023)
Thermokarst lakes are potentially important sources of methane (CH 4 ) and carbon dioxide (CO 2 ). However, considerable uncertainty exists regarding carbon emissions from thermokarst lakes owing to a limited understanding of their patterns and motivators. In this study, we measured CH 4 and CO 2 diffusive fluxes in 163 thermokarst lakes in the Qinghai–Tibet Plateau (QTP) over 3 years from May to October. The median carbon emissions from the QTP thermokarst lakes were 1440 mg CO 2 m −2 day −1 and 60 mg CH 4 m −2 day −1 , respectively. The diffusive rates of CO 2 and CH 4 are related to the catchment land cover type. Sediment microbial abundance and hydrochemistry explain 51.9% and 38.3% of the total variance in CH 4 diffusive emissions, respectively, while CO 2 emissions show no significant relationship with environmental factors. When upscaling carbon emissions from the QTP thermokarst lakes, the annual average CH 4 release per lake area is equal to that of the pan‐Arctic region. Our findings highlight the importance of incorporating in situ observation data with different emission pathways for different land cover types in predicting carbon emissions from thermokarst lakes in the future.

A new series of IDO1 inhibitors derived from microbial metabolites - Jingtong Zhu; Man Yu; Wenbin Shen; Xiao Ren; Haizhou Zheng; Yunlong Mu; Xinhua Lu; Lili Zhai (Phytochemistry Letters, 2023)

Cation mixing effect regulation by niobium for high voltage single-crystalline nickel-rich cathodes - Zhikun Zhao; Chunli Li; Ziyue Wen; Zhuolin Yang; Shijie Lu; Xinyu Zhang; Shi Chen; Borong Wu; Feng Wu; Daobin Mu (Chemical Engineering Journal, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Basal Forebrain Cholinergic Innervation Induces Depression-Like Behaviors Through Ventral Subiculum Hyperactivation - Nana Yu; Huina Song; Guangpin Chu; Xu Zhan; Bo Liu; Yangling Mu; Jian-Zhi Wang; Yisheng Lu (Neuroscience Bulletin, 2023)
Malfunction of the ventral subiculum (vSub), the main subregion controlling the output connections from the hippocampus, is associated with major depressive disorder (MDD). Although the vSub receives cholinergic innervation from the medial septum and diagonal band of Broca (MSDB), whether and how the MSDB-to-vSub cholinergic circuit is involved in MDD is elusive. Here, we found that chronic unpredictable mild stress (CUMS) induced depression-like behaviors with hyperactivation of vSub neurons, measured by c-fos staining and whole-cell patch-clamp recording. By retrograde and anterograde tracing, we confirmed the dense MSDB cholinergic innervation of the vSub. In addition, transient restraint stress in CUMS increased the level of ACh in the vSub. Furthermore, chemogenetic stimulation of this MSDB-vSub innervation in ChAT - Cre mice induced hyperactivation of vSub pyramidal neurons along with depression-like behaviors; and local infusion of atropine, a muscarinic receptor antagonist, into the vSub attenuated the depression-like behaviors induced by chemogenetic stimulation of this pathway and CUMS. Together, these findings suggest that activating the MSDB-vSub cholinergic pathway induces hyperactivation of vSub pyramidal neurons and depression-like behaviors, revealing a novel circuit underlying vSub pyramidal neuronal hyperactivation and its associated depression.

Coupling coordination relationships between air pollutant concentrations and emissions in China - Qian Wu; Song Hong; Lu Yang; Hang Mu; Chaoqing Huang; Xiaoxiao Niu; Yanmei Zhong; Jiahui Yi; Chao He (Atmospheric Pollution Research, 2023)

Silencing P25, HC-Pro and Brp1 of Potato Virus (Viroid) Using Artificial microRNA Confers Resistance to PVX, PVY and PSTVd in Transgenic Potato - Lili Jiang; Rui Mu; Ziquan Wang; Shangwu Liu; Dianqiu Lu (Potato Research, 2023)

Leaf and Soil Phosphatases and the Correlations with Leaf P Resorption of Lucerne Under P Fertilization and Irrigation - Mei Yang; Yixiao Lu; Le Mu; Huimin Yang (Journal of Soil Science and Plant Nutrition, 2023)

The chemical index of alteration in Permo-Carboniferous strata in North China as an indicator of environmental and climate change throughout the late Paleozoic Ice Age - Yanan Li; Longyi Shao; Christopher R. Fielding; Tracy D. Frank; Dewei Wang; Guangyuan Mu; Jing Lu (Global and Planetary Change, 2023)

Liquid metal @ mxene spring supports ionic gel with excellent mechanical properties for high-sensitivity wearable strain sensor - Lisong Dong; Xiaoyao Zhou; Shuxin Zheng; Zhongfan Luo; Yuxiang Nie; Xin Feng; Jiahua Zhu; Zhangzhong Wang; Xiaohua Lu; Liwen Mu (Chemical Engineering Journal, 2023)

Ozone exposure and health risks of different age structures in major urban agglomerations in People’s Republic of China from 2013 to 2018 - Lu Yang; Song Hong; Hang Mu; Jingwei Zhou; Chao He; Qian Wu; Xi Gong (Environmental Science and Pollution Research, 2023)

Spatial distribution characteristics and prediction of fluorine concentration in groundwater based on driving factors analysis - Mu-Yuan Lu; Yuan Liu; Gui-Jian Liu; Yong-Li Li; Jin-Zhao Xu; Guan-Yu Wang (Science of The Total Environment, 2023)

A critical review of sulfate aerosol formation mechanisms during winter polluted periods - Can Ye; Keding Lu; Huan Song; Yujing Mu; Jianmin Chen; Yuanhang Zhang (Journal of Environmental Sciences, 2023)

The textural properties of cooked convenience rice upon repeated freeze–thaw treatments are largely affected by water mobility at grain level - Shiyi Lu; Jie Li; Minghao Xu; Yifan Mu; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Research International, 2023)

Single atom Co-anchored nitrogen‑doped graphene for peroxymonosulfate activation with high selectivity of singlet oxygen generation - Han-Qing Zhao; Jun-Sheng Song; Peili Lu; Yang Mu (Chemical Engineering Journal, 2023)

Hierarchically porous zirconium-based metal–organic frameworks for rapid adsorption and enrichment of sulfonamide antibiotics - Lizhen Han; Peige Qin; Mengyuan Li; Dan Li; Mengyao Mu; Yanmei Gao; Shiping Zhu; Minghua Lu; Zongwei Cai (Chemical Engineering Journal, 2023)

Diosmetin inhibits subchondral bone loss and indirectly protects cartilage in a surgically-induced osteoarthritis mouse model - Hongzhi Ding; Huan Ding; Pei Mu; Xiongwei Lu; Zhixing Xu (Chemico-Biological Interactions, 2023)

A multi-vortex micromixer based on the synergy of acoustics and inertia for nanoparticle synthesis - Yuwen Lu; Wei Tan; Shuoshuo Mu; Guorui Zhu (Analytica Chimica Acta, 2023)

Body mass index–based predictions and personalized clinical strategies for colorectal cancer in the context of PPPM - Yun-Jia Gu; Li-Ming Chen; Mu-En Gu; Hong-Xiao Xu; Jing Li; Lu-Yi Wu (EPMA Journal, 2022)
Currently colorectal cancer (CRC) is the third most prevalent cancer worldwide. Body mass index (BMI) is frequently used in CRC screening and risk assessment to quantitatively evaluate weight. However, the impact of BMI on clinical strategies for CRC has received little attention. Within the framework of the predictive, preventive, and personalized medicine (3PM/PPPM), we hypothesized that BMI stratification would affect the primary, secondary, and tertiary care options for CRC and we conducted a critical evidence-based review. BMI dynamically influences CRC outcomes, which helps avoiding adverse treatment effects. The outcome of surgical and radiation treatment is adversely affected by overweight (BMI ≥ 30) or underweight (BMI < 20). A number of interventions, such as enhanced recovery after surgery and robotic surgery, can be applied to CRC at all levels of BMI. BMI-controlling modalities such as exercise, diet control, nutritional therapy, and medications may be potentially beneficial for patients with CRC. Patients with overweight are advised to lose weight through diet, medication, and physical activity while patients suffering of underweight require more focus on nutrition. BMI assists patients with CRC in better managing their weight, which decreases the incidence of adverse prognostic events during treatment. BMI is accessible, noninvasive, and highly predictive of clinical outcomes in CRC. The cost–benefit of the PPPM paradigm in developing countries can be advanced, and the clinical benefit for patients can be improved with the promotion of BMI-based clinical strategy models for CRC.

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

miR-182-5p Delivered by Plasma Exosomes Promotes Sevoflurane-Induced Neuroinflammation and Cognitive Dysfunction in Aged Rats with Postoperative Cognitive Dysfunction by Targeting Brain-Derived Neurotrophic Factor and Activating NF-κB Pathway - Fu-sheng Wei; Mu-wen Rao; Yuan-lu Huang; Shi-biao Chen; Yu-qian Wu; Lei Yang (Neurotoxicity Research, 2022)

A Novel Slow-Release Fertilizer Derived from Itaconic Acid–Modified Biochar: Synthesis, Characteristics, and Applications in Cucumber Seedlings - Aojie Shang; Kaile Yang; Yaling Lu; Qinghua Jia; Zhong Li; Guocai Ma; Jincheng Mu (Journal of Soil Science and Plant Nutrition, 2022)

Improving the Interpretability and Reliability of Regional Land Cover Classification by U-Net Using Remote Sensing Data - Xinshuang Wang; Jiancheng Cao; Jiange Liu; Xiangwu Li; Lu Wang; Feihang Zuo; Mu Bai (Chinese Geographical Science, 2022)

Fine mapping of powdery mildew and stripe rust resistance genes Pm5V/Yr5V transferred from Dasypyrum villosum into wheat without yield penalty - Ruiqi Zhang; Chuntian Lu; Xiangru Meng; Yali Fan; Jie Du; Runran Liu; Yigao Feng; Liping Xing; Petr Cápal; Kateřina Holušová; Jaroslav Doležel; Yiwei Wang; et al. (Theoretical and Applied Genetics, 2022)

Using hydro-climate elasticity estimator and geographical detector method to quantify the individual and interactive impacts on NDVI in oasis-desert ecotone - Jingjing Chang; Lu Gong; Fanjiang Zeng; Jie Xue; Donglei Mao; Yongxiang Cao; Guijin Mu; Shaoping Wang (Stochastic Environmental Research and Risk Assessment, 2022)

Checking transformation efficiency for different Lagenaria siceraria genotypes by using seed germination pouches as a growth carrier - Ying Wang; Lijuan Huang; Yanwei Li; Zishan Feng; Zihan Mu; Jian Wang; Xinyi Wu; Baogen Wang; Zhongfu Lu; Guojing Li; Xiaohua Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)
Bottle gourd [ Lagenaria siceraria (Mol.) Standl.] is one of the most common horticultural and medicinal crops. Genetic transformation is a rate-limiting step in unraveling the function of genes and molecular breeding in this non-model crop. In this study, we established an optimized protocol for transformation using a seed germination pouch as a growth carrier and developed bottle gourd composite plants. Overground explants were inoculated with Agrobacterium rhizogenes strain R1000, which harbored a binary vector pBI121 carrying the GUS reporter gene. The integration of GUS into transgenic roots was confirmed via reverse transcription-polymerase chain reaction and histochemical staining. Furthermore, we screened for desirable genotypes from 14 bottle gourd germplasm collections based on the number of induced roots, transformation efficiency, and induction rate, and “Changguang” (transformation efficiency, approximately 36.8%) was selected as the genotype suitable for hairy root induction in bottle gourd. The optimized protocol presented here is a rapid, suitable, and efficient tool for studying the function of genes and root biology of bottle gourd in the future.

Identification of the glutamine synthetase (GS) gene family in four wheat species and functional analysis of Ta4D.GSe in Arabidopsis thaliana - Huayan Yin; Qian Sun; Xiaoqing Lu; Lufei Zhang; Yanchao Yuan; Cuiling Gong; Xiaoyan He; Wujun Ma; Ping Mu (Plant Molecular Biology, 2022)
Drought stress can negatively impact crop yield and quality. Improving wheat yields under drought stress is a major objective of agronomic research. Glutamine synthetase (GS) is a key enzyme of nitrogen metabolism that is critical to plant growth and development in abiotic stress response. However, to date, no systemic characterization of the GS genes has yet been conducted in wheat and its close relatives. We identified a total of 15 GS genes in Triticum aestivum (2n = 6x = 42; AABBDD), as well as 9 GS genes in Triticum dicoccoides (2n = 4x = 28; AABB), 6 in Aegilops tauschii (2n = 2x = 14; DD), and 5 in Triticum urartu (2n = 2x = 14; AA). The 35 GSs were further clustered into five lineages according to the phylogenetic tree. Synteny analysis revealed that the three subgenomes in bread wheat retained extensive synteny between bread wheat and its three relative species. We identified three up-regulated TaGSs ( Ta4A.GSe , Ta4B.GSe , and Ta4D.GSe ) from transcriptome data after drought and salt stress. Ta4D.GSe was subsequently used for further functional studies, and its subcellular localization were determined in Arabidopsis protoplasts. Its overexpression in Arabidopsis enhanced drought tolerance by increasing the ability of scavenging of reactive oxygen species (ROS) and osmotic adjustment. We identified GS gene family in four wheat species and performed comparative analyses of their relationships, chromosome locations, conserved motif, gene structure, and synteny. The subcellular localization of Ta4D.GSe was detected and its drought tolerance function was demonstrated. Taken together, these findings provide insight into the potential functional roles of the GS genes in abiotic stress tolerance. Key message This report clearly shows detailed characterization of GS gene family in four wheat species and demonstrates that Ta4D.GSe plays an important role in enhancing drought tolerance by improving the scavenging of ROS and osmotic adjustment ability in Arabidopsis .

Nonlinear dependence between China’s carbon market and stock market: new evidence from quantile coherency and causality-in-quantiles - Yonghong Jiang; Lu Liu; Jinqi Mu (Environmental Science and Pollution Research, 2022)

The IAMAS-CNC Early Career Scientists Nobel Prize Online Interpretation Workshop - Jing Li; Zhongjing Jiang; Yueming Dong; Lu Zhang; Tong Ying; Zhenyu Zhang; Mu Mu (Advances in Atmospheric Sciences, 2022)

Phospholipid Compositions in Portunus trituberculatus Larvae at Different Developmental Stages - Zhibin Lu; Ce Shi; Lei Liu; Changkao Mu; Yangfang Ye; Chunlin Wang (Journal of Ocean University of China, 2022)

Classification of electrocardiogram signals with waveform morphological analysis and support vector machines - Hongqiang Li; Zhixuan An; Shasha Zuo; Wei Zhu; Lu Cao; Yuxin Mu; Wenchao Song; Quanhua Mao; Zhen Zhang; Enbang Li; Juan Daniel Prades García (Medical & Biological Engineering & Computing, 2022)

Disaster characteristics and influence range of earth fissure on nearby structures - Yahong Deng; Jiang Chang; Quanzhong Lu; Li Li; Huandong Mu; Libin Feng (Arabian Journal of Geosciences, 2022)

Cytotoxic benzopyranone and xanthone derivatives from a coral symbiotic fungus Cladosporium halotolerans GXIMD 02502 - Chao-Nan Wang; Hu-Mu Lu; Cheng-Hai Gao; Lang Guo; Zhen-Yu Zhan; Jun-Jian Wang; Yong-Hong Liu; Song-Tao Xiang; Jian Wang; Xiao-Wei Luo (Natural Product Research, 2021)

Random Walks Partitioning and Network Reliability Assessing in Water Distribution System - Tianwei Mu; Yan Lu; Haoqiang Tan; Haowen Zhang; Chengzhi Zheng (Water Resources Management, 2021)

Synchronized research on endothelial dysfunction and microcirculation structure in dorsal skin of rats with type 2 diabetes mellitus - Yajie Wei; Huimin Chen; Qingzhuo Chi; Ying He; Lizhong Mu; Chao Liu; Yunxia Lu (Medical & Biological Engineering & Computing, 2021)

Genome-wide identification and expression analysis of the Brassica oleracea L. chitin-binding genes and response to pathogens infections - Mingzhao Zhu; Shujin Lu; Mu Zhuang; Yangyong Zhang; Honghao Lv; Jialei Ji; Xilin Hou; Zhiyuan Fang; Yong Wang; Limei Yang (Planta, 2021)
Main conclusion Chitinase family genes were involved in the response of Brassica oleracea to Fusarium wilt, powdery mildew, black spot and downy mildew. Abstract Abstract Chitinase, a category of pathogenesis-related proteins, is believed to play an important role in defending against external stress in plants. However, a comprehensive analysis of the chitin-binding gene family has not been reported to date in cabbage ( Brassica oleracea L.), especially regarding the roles that chitinases play in response to various diseases. In this study, a total of 20 chitinase genes were identified using a genome-wide search method. Phylogenetic analysis was employed to classify these genes into two groups. The genes were distributed unevenly across six chromosomes in cabbage, and all of them contained few introns (≤ 2). The results of collinear analysis showed that the cabbage genome contained 1–5 copies of each chitinase gene (excluding Bol035470 ) identified in Arabidopsis . The heatmap of the chitinase gene family showed that these genes were expressed in various tissues and organs. Two genes ( Bol023322 and Bol041024 ) were relatively highly expressed in all of the investigated tissues under normal conditions, exhibiting the expression characteristics of housekeeping genes. In addition, under four different stresses, namely, Fusarium wilt, powdery mildew, black spot and downy mildew, we detected 9, 5, 8 and 8 genes with different expression levels in different treatments, respectively. Our results may help to elucidate the roles played by chitinases in the responses of host plants to various diseases.

Genome-Wide Association Study of Plant and Ear Height in Maize - Shi Lu; Mu Li; Mo Zhang; Ming Lu; Xinqi Wang; Piwu Wang; Wenguo Liu (Tropical Plant Biology, 2020)

Analysis of stress-strain relationship of brittle rock containing microcracks under water pressure - Zhihao Li; Ziming Xiong; Haoxiang Chen; Hao Lu; Mu Huang; Chao Ma; Yiming Liu (Bulletin of Engineering Geology and the Environment, 2020)

Dynamic Detection of Thrombolysis in Embolic Stroke Rats by Synchrotron Radiation Angiography - Liping Wang; Panting Zhou; Zhihao Mu; Xiaojie Lin; Lu Jiang; Zhuo Cheng; Longlong Luo; Zhiming Xu; Jieli Geng; Yongting Wang; Zhijun Zhang; Guo-Yuan Yang (Translational Stroke Research, 2019)

Hydrogen-induced tolerance against osmotic stress in alfalfa seedlings involves ABA signaling - Kiprotich Felix; Jiuchang Su; Rongfei Lu; Gan Zhao; Weiti Cui; Ren Wang; Hualun Mu; Jin Cui; Wenbiao Shen (Plant and Soil, 2019)

TMT-based quantitative proteomics revealed follicle-stimulating hormone (FSH)-related molecular characterizations for potentially prognostic assessment and personalized treatment of FSH-positive non-functional pituitary adenomas - Ya Wang; Tingting Cheng; Miaolong Lu; Yun Mu; Biao Li; Xuejun Li; Xianquan Zhan (EPMA Journal, 2019)

Analysis of DNA Methylation Level of Portunus trituberculatus Subjected to Low Salinity with Methylation-Sensitive Amplification Polymorphism - Shaokun Lu; Ronghua Li; Tianlong Gao; Chunlin Wang; Weibing Zheng; Changkao Mu; Weiwei Song (Journal of Ocean University of China, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Groove structure of porous hydroxyapatite scaffolds (HAS) modulates immune environment via regulating macrophages and subsequently enhances osteogenesis - Chenglong Li; Lu Yang; Xiaohua Ren; Mu Lin; Xiliang Jiang; Daonan Shen; Taotao Xu; Jing Ren; Lijuan Huang; Wei Qing; Jiajun Zheng; Yandong Mu (JBIC Journal of Biological Inorganic Chemistry, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Calculation of an Adequate Intake (AI) Value and Safe Range of Selenium (Se) for Chinese Infants 0–3 Months Old Based on Se Concentration in the Milk of Lactating Chinese Women with Optimal Se Intake - Feng Han; Liping Liu; Jiaxi Lu; Yingjuan Chai; Jie Zhang; Shijin Wang; Licui Sun; Qin Wang; Yiqun Liu; Mengjie He; Weipeng Mu; Zhenwu Huang (Biological Trace Element Research, 2019)

The complete maternal mitochondrial genome sequence of Cuneopsis heudei (Bivalvia: Unionoida: Unionidae) - Qishuo Wang; Lu Ma; Lin Li; Ruijuan Feng; Huan Mu; Xin Wang; Cheng Wang; Xuepeng Wang (Conservation Genetics Resources, 2018)

Insertion of a solo LTR retrotransposon associates with spur mutations in ‘Red Delicious’ apple (Malus × domestica) - Mengxue Han; Qibao Sun; Junyong Zhou; Huarong Qiu; Jing Guo; Lijuan Lu; Wenlei Mu; Jun Sun (Plant Cell Reports, 2017)

An Inframe Trinucleotide Deletion in MTRR Exon 1 is Associated with the Risk of Spina Bifida - Jun Zhang; Xiao-lu Dai; Gui-cen Liu; Juan Wang; Xue-yi Ren; Mu-hua Jin; Nan-nan Mi; Shu-qin Wang (NeuroMolecular Medicine, 2017)

IGF-II-mediated downregulation of peroxisome proliferator-activated receptor-γ coactivator-1α in myoblast cells involves PI3K/Akt/FoxO1 signaling pathway - Xiaoyu Mu; Weihong Qi; Yunzhang Liu; Jianfeng Zhou; Yun Li; Xiaozhi Rong; Ling Lu (Molecular and Cellular Biochemistry, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Optimization of continuous-flow solid-phase denitrification via coupling carriers in enhancing simultaneous removal of nitrogen and organics for agricultural runoff purification - Yi Lu; Xiaoqing Zhang; Lijuan Feng; Guangfeng Yang; Zhou Zheng; Junzhi Liu; Jun Mu (Biodegradation, 2017)

Efficacy and safety of metformin and sitagliptin based triple antihyperglycemic therapy (STRATEGY): a multicenter, randomized, controlled, non-inferiority clinical trial - Wen Xu; Yiming Mu; Jiajun Zhao; Dalong Zhu; Qiuhe Ji; Zhiguang Zhou; Bin Yao; Anhua Mao; Samuel S. Engel; Bin Zhao; Yan Bi; Longyi Zeng; et al. (Science China Life Sciences, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

Relationship between lightning activity and tropospheric nitrogen dioxide and the estimation of lightning-produced nitrogen oxides over China - Fengxia Guo; Xiaoyu Ju; Min Bao; Ganyi Lu; Zupei Liu; Yawen Li; Yijun Mu (Advances in Atmospheric Sciences, 2017)

Rapid Fabrication of a Cell-Seeded Collagen Gel-Based Tubular Construct that Withstands Arterial Pressure - Ho-Yi Tuan-Mu; Po-Ching Lu; Pei-Yuan Lee; Chien-Chih Lin; Chun-Jung Chen; Lynn L.H. Huang; Jia-Horng Lin; Jin-Jia Hu (Annals of Biomedical Engineering, 2016)

Non-integrating lentiviral vectors based on the minimal S/MAR sequence retain transgene expression in dividing cells - Zhen Xu; Feng Chen; Lingling Zhang; Jing Lu; Peng Xu; Guang Liu; Xuemin Xie; Wenli Mu; Yajun Wang; Depei Liu (Science China Life Sciences, 2016)

Baseline sensitivity and control efficacy of antibiosis fungicide tetramycin against Botrytis cinerea - Yingying Song; Leiming He; Lele Chen; Yupeng Ren; Hongbao Lu; Su Geng; Wei Mu; Feng Liu (European Journal of Plant Pathology, 2016)

Recent research progress and prospects in tourism geography of China - Lin Lu; Jie Bao; Jianfeng Huang; Qijing Zhu; Chenglin Mu; Xiaole Chu; Yan Xu; Xiaoli Zha (Journal of Geographical Sciences, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Seasonal difference of human adenoviruses in a subtropical river basin based on 1-year monthly survey - Chi-Wei Tao; Bing-Mu Hsu; Po-Min Kao; Wen-Chien Huang; Tsui-Kang Hsu; Ying-Ning Ho; Yen-Ju Lu; Cheng-Wei Fan (Environmental Science and Pollution Research, 2016)

Baseline sensitivity and efficacy of the sterol biosynthesis inhibitor triflumizole against Botrytis cinerea - Yingying Song; Datong Xu; Hongbao Lu; Leiming He; Lele Chen; Junan Shao; Chunmei Xu; Wei Mu; Feng Liu (Australasian Plant Pathology, 2016)

Glucocorticoid Receptor β Acts as a Co-activator of T-Cell Factor 4 and Enhances Glioma Cell Proliferation - Qian Wang; Pei-Hua Lu; Zhi-Feng Shi; Yan-Juan Xu; Jie Xiang; Yan-Xia Wang; Ling-Xiao Deng; Ping Xie; Ying Yin; Bin Zhang; Hui-Jun Mu; Wei-Zhen Qiao; et al. (Molecular Neurobiology, 2015)

Two new triterpenoid saponins obtained by microbial hydrolysis with Alternaria alternata AS 3.6872 - Li-Hua Mu; Yong-Jie Gu; Bai-Ping Ma; Li Lu; Ping Liu (Natural Product Research, 2015)

A novel MVK missense mutation in one Chinese family with disseminated superficial actinic porokeratosis - Wen-sheng Lu; Xiao-dong Zheng; Xiu-hua Yao; Lan-fang Zhang; Mu-Qiu Wang; Fa-Xing Jiang; Si-Ping Zhang; Bai Hu (Molecular Biology Reports, 2014)

Overexpression of a dominant-negative mutant of SIRT1 in mouse heart causes cardiomyocyte apoptosis and early-onset heart failure - WenLi Mu; QingJun Zhang; XiaoQiang Tang; WenYan Fu; Wei Zheng; YunBiao Lu; HongLiang Li; YuSheng Wei; Li Li; ZhiGang She; HouZao Chen; DePei Liu (Science China Life Sciences, 2014)

Rice black-streaked dwarf virus genome segment S5 is a bicistronic mRNA in infected plants - Jian Yang; Heng-Mu Zhang; Lu Ying; Jing Li; Ming-Fang Lv; Li Xie; Pei-Pei Li; Xiao-Ya Liu; Dai Liang-Ying; Jian-Ping Chen (Archives of Virology, 2014)

Clinical and laboratory characteristics of patients having amyloidogenic transthyretin deposition in osteoarthritic knee joints - Ya-Jun Gu; Peng Ge; Yun Mu; Jin-Hai Lu; Fang Zheng; Xu-Guo Sun (Journal of Zhejiang University-SCIENCE B, 2014)

Molecular cloning and expression analysis of glutathione peroxidase and glutathione reductase from Gracilaria lemaneiformis under heat stress - Ning Lu; Yan Ding; Xiao-Nan Zang; Xue-Cheng Zhang; Hao Chen; Xiao-Sheng Mu (Journal of Applied Phycology, 2013)

Significantly differential diffusion of neuropathological aggregates in the brain of transgenic mice carrying N-terminal mutant huntingtin fused with green fluorescent protein - Pei-Hsun Cheng; Chia-Ling Li; Lu-Shiun Her; Yu-Fan Chang; Anthony W. S. Chan; Chuan-Mu Chen; Shang-Hsun Yang (Brain Structure and Function, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

No Association of Angiotensin I Converting Enzyme I/D Polymorphism with Domain-Specific Cognitive Function in Aged Men without Dementia - Mu-En Liu; Shih-Jen Tsai; Ti Lu; Cheng-Jee Hong; Ming-Chao Chen; Shoa-Lin Lin; Heng-Liang Yeh; Yan-Chiou Ku (NeuroMolecular Medicine, 2011)

Effect of trichostatin A and 5-Aza-2′-deoxycytidine on transgene reactivation and epigenetic modification in transgenic pig fibroblast cells - Qingran Kong; Meiling Wu; Zhenkun Wang; Xinmiao Zhang; Lu Li; Xiangyu Liu; Yanshuang Mu; Zhonghua Liu (Molecular and Cellular Biochemistry, 2011)

Impacts of soil conservation on groundwater recharge in the semi-arid Loess Plateau, China - John B. Gates; Bridget R. Scanlon; Xingmin Mu; Lu Zhang (Hydrogeology Journal, 2011)

Soil erosion changes over the past five decades in the red soil region of Southern China - Yin Liang; Decheng Li; Xixi Lu; Xuan Yang; Xianzhang Pan; Huan Mu; Deming Shi; Bin Zhang (Journal of Mountain Science, 2010)

Alu tandem sequences inhibit GFP gene expression by triggering chromatin wrapping - Xiu-Fang Wang; Xiaoyan Wang; Jing Liu; Jingjing Feng; Wenli Mu; Xiaojuan Shi; QinQing Yang; Xiaocui Duan; Ying Xie; Zhanjun Lu (Genes & Genomics, 2009)

Impact of consistent boundary layer mixing approaches between NAM and CMAQ - Pius Lee; Youhua Tang; Daiwen Kang; Jeff McQueen; Marina Tsidulko; Ho-Chun Huang; Sarah Lu; Mary Hart; Hsin-Mu Lin; Shaocai Yu; Geoff DiMego; Ivanka Stajner; et al. (Environmental Fluid Mechanics, 2009)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Hypertonic saline resuscitation maintains a more balanced profile of T-lymphocyte subpopulations in a rat model of hemorrhagic shock - Yuan-qiang Lu; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mu; Wei-dong Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Isolation and characterization of a novel thermophilic Bacillus strain degrading long-chain n-alkanes - Lei Wang; Yun Tang; Shuo Wang; Ru-Lin Liu; Mu-Zhi Liu; Yan Zhang; Feng-Lai Liang; Lu Feng (Extremophiles, 2006)

Pharmacokinetic study with N-Ile1-Thr2-63-desulfato-r-hirudin in rabbits by means of bioassay - Guo-zhu Han; Hong-can Ren; Yong Lu; Ying Li; Shu Xiao; Hong-wei Ye; He-mu Wang (Journal of Zhejiang University-SCIENCE B, 2006)

Unfolding of titin domains studied by molecular dynamics simulations - Mu Gao; Hui Lu; Klaus Schulten (Journal of Muscle Research and Cell Motility, 2002)